Selective catalytic reduction suspension
Patent Information
- Application Number
- JP2021566194
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-06
- Filing Date
- 2020-05-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-05-05
Smart Images

Figure 0007631229000001 
Figure 0007631229000002 
Figure 0007631229000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous suspension, a method for producing said aqueous suspension and a method for producing a selective catalytic reduction catalyst using said aqueous suspension. The present invention further relates to a selective catalytic reduction obtained or obtainable by the above mentioned method. [Background technology]
[0002] Selective catalytic reduction (SCR) catalysts in which vanadium and tungsten are supported on an oxide material, e.g., titania, are well known. Typical methods, including precipitation, for producing these titania particles in the catalyst focus on small particles with an average particle size in the range of 1-3 micrometers. However, it has become apparent that there are some problems with washcoat adhesion for such SCR catalysts. US2015 / 0005158A1 discusses the optimization of washcoat adhesion for hydrocarbon conversion catalysts on metal substrates. This document generally highlights the difficulties of adhesion for SCR catalysts, both zeolite-based SCR catalysts and TiO2-based SCR catalysts. Thus, there was a further need to provide improved suspensions and improved methods for producing selective catalytic reduction catalysts using said suspensions to improve washcoat adhesion on substrates while maintaining or improving the catalytic activity of the selective catalytic reduction catalyst. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] US2015 / 0005158A1 Summary of the Invention [Problem to be solved by the invention]
[0004] It was therefore an object of the present invention to provide an aqueous suspension and a method for producing a selective catalytic reduction catalyst using said suspension that exhibits improved washcoat adhesion onto a substrate, while maintaining or improving the catalytic activity of the selective catalytic reduction catalyst.
[0005] Surprisingly, it has been found that the use of the aqueous suspension according to the invention in a method for producing a selective catalytic reduction catalyst makes it possible to improve the washcoat adhesion onto the substrate while maintaining or improving the catalytic activity of the selective catalytic reduction catalyst. [Means for solving the problem]
[0006] Accordingly, the present invention provides an aqueous suspension comprising water, one or more sources of vanadium oxide and tungsten oxide, and particles of an oxide support, the suspension comprising: The particles of the aqueous suspension exhibit a multimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve being in the range of 0.5 to 15 micrometers. Peak particle size value M(I)( Maximum value M(I) ) A first peak having a peak size in the range of 1 to 40 micrometers Peak particle size value M(II)( Maximum value M(II) ) wherein (M(I) / μm):(M(II) / μm)<1:1; Concerning aqueous suspensions. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 shows the particle size distribution of the final suspension prepared in Example 1.1. [Diagram 2] FIG. 2 shows the particle size distribution of the final suspension produced in Comparative Example 1. [Diagram 3] FIG. 3 shows the particle size distribution of the Ce / Zr mixed oxide used to prepare example 1.2. [Figure 4] FIG. 4 shows the particle size distribution of the suspension containing the Ce / Zr mixed oxide after grinding in example 1.2. [Diagram 5] FIG. 5 shows the particle size distribution of the final suspension prepared in Example 1.2. [Figure 6] FIG. 6 shows the washcoat loss measured for the catalytic coatings of Comparative Example 1 and Examples 1.1 and 1.2. [Figure 7] FIG. 7 shows the DeNOx performance of the catalysts of Examples 3.1 and 3.2 measured at high NO2 / NOx ratios at an SCR-inlet temperature of 270° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Preferably, the particles in the aqueous suspension exhibit a bimodal particle size distribution.
[0009] Indeed, it has been found that the introduction of a multimodal particle size distribution into an aqueous suspension for producing a selective catalytic reduction catalyst improves washcoat adhesion as well as the catalytic activity of the resulting catalyst.
[0010] In the context of the present invention it is preferred that the aqueous suspension further comprises particles of a mixed oxide comprising cerium.
[0011] With respect to the mixed oxide, it is preferred that the mass ratio of the mixed oxide to the oxide support is in the range of 1:1 to 1:10, more preferably in the range of 1:1.5 to 1:8, more preferably in the range of 1:2 to 1:7, more preferably in the range of 1:2.5 to 1:5.
[0012] With regard to the mixed oxide, it is preferred that it further comprises one or more of zirconium, niobium, molybdenum, lanthanum, yttrium, neodymium, praseodymium and hafnium, more preferably one or more of zirconium, lanthanum, praseodymium, yttrium and hafnium, more preferably one or more of zirconium, praseodymium, lanthanum and hafnium. More preferred is that the mixed oxide further comprises zirconium, praseodymium, lanthanum and hafnium. 20-60% by weight, more preferably 30-50% by weight, more preferably 35-45% by weight of the mixed oxide consists of cerium calculated as CeO2, and 40-80% by weight, more preferably 50-70% by weight, more preferably 55-65% by weight of the mixed oxide consists of ZrO2, Pr6O, respectively. 11 More preferably, the mixed oxide consists of zirconium, praseodymium, lanthanum and hafnium, calculated as La2O3 and HfO2. More preferably, 30 to 60% by weight, more preferably 40 to 55% by weight, and even more preferably 45 to 55% by weight of the mixed oxide consists of zirconium, calculated as ZrO2.
[0013] It is preferred that 95 to 100% by mass, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass, and even more preferably 99.5 to 100% by mass of the mixed oxide consists of cerium, oxygen, zirconium, praseodymium, lanthanum and hafnium.
[0014] It is preferred that the aqueous suspension contains the mixed oxide in an amount in the range of 10 to 50% by mass, more preferably 20 to 45% by mass, more preferably 25 to 40% by mass, more preferably 25 to 35% by mass, based on the mass of the oxide support.
[0015] With regard to the particles of the cerium-containing mixed oxide, it is preferred that these exhibit a unimodal or multimodal particle size distribution, more preferably a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 herein.
[0016] In the context of the present invention, it is preferred that (M(II) / μm)-(M(I) / μm)≧0.5, more preferably 0.5≦(M(II) / μm)-(M(I) / μm)≦20, more preferably 1.5≦(M(II) / μm)-(M(I) / μm)≦15.
[0017] Accordingly, the present invention preferably provides a suspension comprising water, one or more sources of vanadium oxide and tungsten oxide, and particles of an oxide support, wherein the particles of the aqueous suspension exhibit a multimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve being in the range of 0.5 to 15 micrometers. Peak Particle Size A first peak having a value M(I) and a peak in the range of 1 to 40 micrometers Peak Particle Size and wherein (M(I) / μm):(M(II) / μm)<1:1, and wherein (M(II) / μm)-(M(I) / μm)≧0.5, more preferably 0.5≦(M(II) / μm)-(M(I) / μm)≦20, and more preferably 1.5≦(M(II) / μm)-(M(I) / μm)≦15.
[0018] Instead, the present invention preferably provides a suspension comprising water, one or more sources of vanadium oxide and tungsten oxide, particles of a mixed oxide comprising cerium, and particles of an oxide support, wherein the particles of the aqueous suspension exhibit a multimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve being in the range of 0.5 to 15 micrometers. Peak Particle Size A first peak having a value M(I) and a peak in the range of 1 to 40 micrometers Peak Particle Sizeand wherein (M(I) / μm):(M(II) / μm)<1:1, and wherein (M(II) / μm)-(M(I) / μm)≧0.5, more preferably 0.5≦(M(II) / μm)-(M(I) / μm)≦20, more preferably 1.5≦(M(II) / μm)-(M(I) / μm)≦15. In accordance with said alternative, it is even more preferred that 3≦(M(II) / μm)-(M(I) / μm)≦12, more preferably 4≦(M(II) / μm)-(M(I) / μm)≦10.
[0019] In the context of the present invention, it is preferred that M(I) is in the range of 0.5 to 5 micrometers, more preferably in the range of 0.7 to 4 micrometers, more preferably in the range of 0.8 to 3.5 micrometers, more preferably in the range of 0.9 to 3 micrometers, more preferably in the range of 1 to 2.5 micrometers, more preferably in the range of 1.25 to 2 micrometers.
[0020] It is preferred that M(II) is in the range of 5.5 to 40 micrometers, more preferably in the range of 6 to 20 micrometers, more preferably in the range of 6.25 to 15 micrometers, more preferably in the range of 6.5 to 10 micrometers, more preferably in the range of 6.75 to 9 micrometers. It is more preferred that the relationship between M(I) and M(II) and their respective values are as defined above.
[0021] With regard to M(I) and M(II), when the aqueous suspension does not contain mixed oxides, it is preferred that M(I) is in the range of 0.5 to 5 micrometers, more preferably in the range of 0.7 to 4 micrometers, more preferably in the range of 0.8 to 3.5 micrometers, more preferably in the range of 0.9 to 3 micrometers, more preferably in the range of 1 to 2.5 micrometers, more preferably in the range of 1.25 to 2 micrometers, and M(II) is in the range of 5.5 to 40 micrometers, more preferably in the range of 6 to 20 micrometers, more preferably in the range of 6.25 to 15 micrometers, more preferably in the range of 8 to 15 micrometers, more preferably in the range of 10 to 15 micrometers.
[0022] With regard to M(I) and M(II), when the aqueous suspension comprises mixed oxides, it is preferred that M(I) is in the range of 0.5 to 5 micrometers, more preferably in the range of 0.7 to 4 micrometers, more preferably in the range of 0.8 to 3.5 micrometers, more preferably in the range of 0.9 to 3 micrometers, more preferably in the range of 1 to 2.5 micrometers, more preferably in the range of 1.25 to 2 micrometers, and M(II) is in the range of 5.5 to 40 micrometers, more preferably in the range of 6 to 20 micrometers, more preferably in the range of 6.25 to 15 micrometers, more preferably in the range of 6.5 to 10 micrometers, more preferably in the range of 6.75 to 9 micrometers.
[0023] With regard to the particles of the aqueous suspension, it is preferred that they have a Dv10 in the range of 0.01 to 3 micrometers, preferably in the range of 0.1 to 2.5 micrometers, more preferably in the range of 0.25 to 2 micrometers, more preferably in the range of 0.4 to 1.5 micrometers. When the aqueous suspension does not contain particles of a mixed oxide containing cerium, it is preferred that the particles of the aqueous suspension have a Dv10 in the range of 0.01 to 3 micrometers, more preferably in the range of 0.1 to 2.5 micrometers, more preferably in the range of 0.25 to 2 micrometers, more preferably in the range of 0.4 to 1.5 micrometers, more preferably in the range of 0.4 to 0.75 micrometers, with Dv10 being determined according to Reference Example 1 of the present specification. When the aqueous suspension contains particles of a mixed oxide containing cerium, it is preferred that the particles of the aqueous suspension have a Dv10 in the range of 0.01 to 3 micrometers, more preferably in the range of 0.1 to 2.5 micrometers, more preferably in the range of 0.25 to 2 micrometers, more preferably in the range of 0.4 to 1.5 micrometers, with Dv10 being determined according to Reference Example 1 of the present specification. More preferably, the particles of the aqueous suspension have a Dv10 in the range of 0.5 to 1.25 micrometers, more preferably in the range of 0.6 to 0.75 micrometers, with Dv10 being determined according to Reference Example 1 herein.
[0024] In the context of the present invention, it is preferred that the particles of the aqueous suspension have a Dv50 in the range of 0.2 to 10 micrometers, more preferably in the range of 0.5 to 7 micrometers, more preferably in the range of 0.75 to 4 micrometers, more preferably in the range of 0.9 to 3 micrometers, more preferably in the range of 1 to 2.5 micrometers, the Dv50 being determined according to Reference Example 1 herein.
[0025] In the context of the present invention, the particles of the aqueous suspension preferably have a Dv90 in the range of 1 to 30 micrometers, more preferably in the range of 1.5 to 20 micrometers, more preferably in the range of 1.75 to 10 micrometers, more preferably in the range of 2 to 5 micrometers, more preferably in the range of 2 to 4 micrometers, said Dv90 being determined according to Reference Example 1 herein.
[0026] The aqueous suspension preferably has a solids content in the range of 10 to 60 mass %, more preferably in the range of 20 to 55 mass %, more preferably in the range of 30 to 50 mass %, and more preferably in the range of 35 to 45 mass %, relative to the mass of the aqueous suspension.
[0027] It is preferred that the suspension has a pH in the range of 2 to 12, more preferably in the range of 3 to 10, more preferably in the range of 4 to 9, more preferably in the range of 5 to 8, more preferably in the range of 6 to 7.5.
[0028] The suspension had a viscosity of 20-200 mPa, measured at 300 revolutions per second. * s range, more preferably 50 to 100 mPa * It is preferred that the viscosity of the composition is in the range of s.
[0029] The aqueous suspension preferably comprises a source of vanadium oxide, more preferably the source of vanadium oxide is selected from the group consisting of vanadium oxalate solution, ammonium metavanadate, and mixtures of two or more thereof, more preferably a vanadium oxalate solution.
[0030] The aqueous suspension preferably comprises a source of vanadium oxide, calculated as V2O5, in an amount in the range of 1.5 to 8% by weight, more preferably in the range of 2 to 7% by weight, more preferably in the range of 3 to 6% by weight, relative to the weight of the oxide support.
[0031] The particles of the oxide support preferably exhibit a multimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein. Alternatively, the particles of the oxide support preferably exhibit a unimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein.
[0032] When the aqueous suspension does not contain particles of a cerium-containing mixed oxide, it is preferred that the particles of the oxide support exhibit a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 herein.When the aqueous suspension contains particles of a cerium-containing mixed oxide, it is preferred that the particles of the oxide support exhibit a unimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 herein.
[0033] Preferably, the oxide support comprises one or more of titanium, silicon, zirconium, and tungsten, more preferably one or more of titanium, silicon, and zirconium, more preferably one or more of titanium, silicon, and tungsten, more preferably titania.More preferably, the oxide support comprises titania and one or more of tungsten and silicon.
[0034] More preferably, the oxide support comprises tungsten in addition to titania. Alternatively, more preferably, the oxide support comprises tungsten and silicon in addition to titania.
[0035] It is preferable that 95 to 100 mass%, more preferably 98 to 100 mass%, more preferably 99 to 100 mass%, and more preferably 99.5 to 100 mass% of the oxide support consists of titania, more preferably consists of one or more of tungsten and silicon, more preferably consists of tungsten, or more preferably consists of tungsten and silicon.
[0036] It is more preferable that 70 to 99 mass%, more preferably 75 to 95 mass%, more preferably 80 to 90 mass%, and more preferably 85 to 90 mass% of the oxide support is made of titania. When the oxide support contains titania, tungsten, and silicon, it is preferable that 0.5 to 15 mass%, more preferably 3 to 15 mass%, and more preferably 6 to 12 mass% of the oxide support is made of tungsten calculated as WO3, and 0.5 to 15 mass%, more preferably 2 to 10 mass%, and more preferably 4 to 8 mass% of the oxide support is made of silicon calculated as SiO2.
[0037] It is preferred that 40 to 90% by mass, more preferably 50 to 85% by mass, and even more preferably 55 to 80% by mass of the aqueous suspension is made up of water.
[0038] It is preferred that the aqueous suspension further comprises an acid, more preferably an organic acid. It is more preferred that the organic acid is selected from the group consisting of acetic acid, tartaric acid, formic acid, lactic acid, oxalic acid and mixtures of two or more thereof, more preferably selected from the group consisting of acetic acid, tartaric acid, formic acid, oxalic acid and mixtures of two or more thereof, more preferably selected from the group consisting of acetic acid, tartaric acid and mixtures of two or more thereof. It is more preferred that the organic acid is tartaric acid. It should be noted that the acid can be used as a rheology modifier. It is more preferred that the acid is used as a rheology modifier.
[0039] Preferably, the aqueous suspension further comprises one or more dispersing agents, more preferably the dispersing agent is an organic polymer, more preferably the organic polymer is an acrylic polymer.
[0040] Preferably, the aqueous suspension further comprises a source of oxidized binder, more preferably selected from the group consisting of alumina, silica, zirconia, and mixtures of two or more thereof, more preferably selected from the group consisting of alumina, silica, and mixtures of two or more thereof, more preferably silica. More preferably, the source of oxidized binder is colloidal silica.
[0041] Preferably, the aqueous suspension comprises 0-0.1% by weight, more preferably 0-0.01% by weight, more preferably 0-0.001% by weight of zeolitic material, more preferably molecular sieves. It is to be understood that in the context of the present invention, the aqueous suspension is preferably substantially free, more preferably free of zeolitic material, more preferably molecular sieves.
[0042] Preferably, the aqueous suspension consists of 0-0.01% by weight, more preferably 0-0.001% by weight, more preferably 0-0.0001% by weight, more preferably 0-0.0001% by weight of copper, more preferably copper and iron. It is to be understood that in the context of the present invention, the aqueous suspension is preferably substantially free, more preferably free, of copper and iron.
[0043] It is preferred that the aqueous suspension comprises 0-0.01% by weight, more preferably 0-0.001% by weight, more preferably 0-0.0001% by weight, more preferably 0-0.00001% by weight, more preferably 0-0.00001% by weight, more preferably platinum group metals. In the context of the present invention, it is to be understood that the aqueous suspension is preferably substantially free, more preferably free, of platinum, more preferably platinum and palladium, more preferably platinum, palladium and rhodium. It is more preferred that the aqueous suspension is substantially free, more preferably free, of platinum group metals.
[0044] The aqueous suspension, 98-100% by weight, more preferably 99-100% by weight, more preferably 99.5-100% by weight, preferably consists of water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, preferably one or more acids as defined above, a dispersing agent as defined above and a source of an oxidized binder as defined above. More preferably, the aqueous suspension consists of water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, more preferably one or more acids as defined above, a dispersing agent as defined above and a source of an oxidized binder as defined above.
[0045] Alternatively, it is preferred that the aqueous suspension, 98-100% by weight, more preferably 99-100% by weight, more preferably 99.5-100% by weight, consists of water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, particles of a mixed oxide comprising cerium as defined above, more preferably one or more of an acid as defined above, a dispersing agent as defined above and a source of oxidized binder as defined above, more preferably an acid as defined above, a dispersing agent as defined above and a source of oxidized binder as defined above. More preferably, the aqueous suspension consists of water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, particles of a mixed oxide comprising cerium as defined above, more preferably one or more of an acid as defined above, a dispersing agent as defined above and a source of an oxidized binder as defined above, more preferably an acid as defined above, a dispersing agent as defined above and a source of an oxidized binder as defined above.
[0046] The present invention relates to a method for producing an aqueous suspension according to the invention, comprising the steps of: (i) optionally preparing an aqueous suspension comprising water and particles of a mixed oxide comprising cerium, said mixed oxide being preferably a mixed oxide as defined above, and the particles of the mixed oxide contained in said aqueous suspension exhibit a monomodal particle size distribution, or Optionally, a step of preparing an aqueous suspension comprising water and particles of a mixed oxide comprising cerium, said mixed oxide being preferably a mixed oxide as defined above, and wherein the mixed oxide particles contained in said aqueous suspension exhibit a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve being in the range of 0.5 to 20 micrometers. Peak Particle Size A first peak having a value M1 and a peak in the range of 1 to 50 micrometers Peak Particle Size a second peak having a value M2, where (M1 / μm):(M2 / μm)<1:1; (ii) producing an aqueous suspension comprising water and one or more sources of vanadium oxide and tungsten oxide, said one or more sources of vanadium oxide and tungsten oxide being preferably one or more sources of vanadium oxide and tungsten oxide as defined above, and further comprising oxide support particles, wherein the oxide support particles contained in said aqueous suspension exhibit a unimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve comprising a peak having a maximum value in the range of 0.5 to 5 micrometers, preferably in the range of 0.7 to 4 micrometers, more preferably in the range of 0.8 to 3.5 micrometers, more preferably in the range of 0.9 to 3 micrometers, more preferably in the range of 1 to 2.5 micrometers, more preferably in the range of 1.25 to 2 micrometers, or wherein the oxide support particles contained in said aqueous suspension exhibit a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, (iii) mixing the suspension from (ii) optionally with the suspension from (i) to obtain an aqueous suspension comprising water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, and optionally particles of a mixed oxide comprising cerium, wherein the particles of the aqueous suspension exhibit a multimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein, said particle size distribution curve being in the range of 0.5 to 15 micrometers. Peak Particle Size A first peak having a value M(I) and a peak in the range of 1 to 40 micrometers Peak Particle Size a second peak having a value M(II), where (M(I) / μm):(M(II) / μm)<1:1 The present invention further relates to a method comprising the steps of:
[0047] (i) The method of the present invention comprises the steps of: (i) producing an aqueous suspension comprising water and particles of a mixed oxide comprising cerium, said mixed oxide being preferably a mixed oxide as defined above, and the mixed oxide particles contained in said aqueous suspension exhibit a monomodal particle size distribution, or A process for producing an aqueous suspension comprising water and particles of a mixed oxide comprising cerium, said mixed oxide being preferably a mixed oxide as defined above, and the mixed oxide particles contained in said aqueous suspension exhibit a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve being in the range of 0.5 to 20 micrometers. Peak Particle Size A first peak having a value M1 and a peak in the range of 1 to 50 micrometers Peak Particle Size a second peak having a value M2, where (M1 / μm):(M2 / μm)<1:1; (ii) producing an aqueous suspension comprising water and one or more sources of vanadium oxide and tungsten oxide, said one or more sources of vanadium oxide and tungsten oxide being preferably one or more sources of vanadium oxide and tungsten oxide as defined above, and further comprising oxide support particles, wherein the oxide support particles contained in said aqueous suspension exhibit a unimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve comprising a peak having a maximum value in the range of 0.5 to 5 micrometers, preferably in the range of 0.7 to 4 micrometers, more preferably in the range of 0.8 to 3.5 micrometers, more preferably in the range of 0.9 to 3 micrometers, more preferably in the range of 1 to 2.5 micrometers, more preferably in the range of 1.25 to 2 micrometers, or the oxide support particles contained in said aqueous suspension exhibit a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, (iii) mixing the suspension from (ii) with the suspension from (i) to obtain an aqueous suspension comprising water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support and particles of a mixed oxide comprising cerium, wherein the particles of the aqueous suspension exhibit a multimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein, said particle size distribution curve comprising a first peak having a maximum value M(I) in the range of 0.5 to 15 micrometers and a second peak having a maximum value M(I) in the range of 1 to 40 micrometers. Peak Particle Size a second peak having a value M(II), where (M(I) / μm):(M(II) / μm)<1:1 It is preferred that the compound contains
[0048] The suspension obtained in (i) preferably has a solid content in the range of 20 to 50% by mass, more preferably in the range of 25 to 45% by mass, more preferably in the range of 30 to 40% by mass, based on the mass of the suspension.
[0049] With regard to (i), it is preferred that the process further comprises the step of adding an acid, the acid more preferably being an acid as defined above.
[0050] It is preferred that (M2 / μm)-(M1 / μm)≧0.5, more preferably 0.5≦(M2 / μm)-(M1 / μm)≦30, more preferably 5≦(M2 / μm)-(M1 / μm)≦25, more preferably 10≦(M2 / μm)-(M1 / μm)≦23. It is even more preferred that 13≦(M2 / μm)-(M1 / μm)≦19.
[0051] The particle size distribution of the aqueous suspension obtained according to (i) is characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, and said particle size distribution curve is in the range of 0.5 to 8 micrometers. Peak Particle Size It preferably comprises a first peak having a value M1 and a second peak having a maximum value M2 in the range of 9 to 50 micrometers.
[0052] According to (i), M1 is preferably in the range of 1.25 to 6 micrometers, more preferably in the range of 1.75 to 4 micrometers, more preferably in the range of 1.85 to 3 micrometers, and according to (i), M2 is preferably in the range of 9 to 35 micrometers, more preferably in the range of 10 to 25 micrometers, more preferably in the range of 12 to 25 micrometers.
[0053] The particles of the suspension obtained according to (i) have a Dv10 in the range of 0.2 to 8 micrometers, more preferably in the range of 0.45 to 5 micrometers, more preferably in the range of 0.5 to 4 micrometers, more preferably in the range of 0.6 to 2.5 micrometers, more preferably in the range of 0.8 to 1.25 micrometers, wherein Dv10 is preferably determined according to Reference Example 1 of the present specification.
[0054] The particles of the suspension obtained according to (i) preferably have a Dv50 in the range of 1 to 25 micrometers, more preferably in the range of 1.5 to 10 micrometers, more preferably in the range of 1.75 to 7 micrometers, more preferably in the range of 2 to 4 micrometers, the Dv50 being determined according to Reference Example 1 herein.
[0055] The particles of the suspension obtained according to (i) have a Dv90 in the range of 3 to 30 micrometers, more preferably in the range of 6 to 25 micrometers, more preferably in the range of 8 to 20 micrometers, more preferably in the range of 10 to 18 micrometers, more preferably in the range of 12 to 16 micrometers, wherein Dv90 is preferably determined according to Reference Example 1 herein.
[0056] (i) preparing an aqueous suspension according to (i.1') providing particles of a mixed oxide comprising cerium, the mixed oxide particles exhibiting a monomodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein, said particle size distribution curve comprising a peak having a maximum value in the range of 5.5 to 40 micrometers, more preferably in the range of 6 to 20 micrometers, more preferably in the range of 6.25 to 15 micrometers, more preferably in the range of 6.5 to 10 micrometers, more preferably in the range of 6.75 to 9 micrometers, (i.2') preparing an aqueous suspension comprising suspending the particles provided in (i.1') in water. Alternatively, it is preferred that the step of producing the aqueous suspension according to (i) comprises: (i.1) A step of providing particles of a mixed oxide comprising cerium, the mixed oxide particles exhibiting a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve being in the range of 0.5 to 30 micrometers Peak Particle Size A first peak having a value M1' and a peak in the range of 1 to 60 micrometers Peak Particle Size a second peak having a value M2', where (M1' / μm):(M2' / μm)<1:1; (i.2) preparing an aqueous suspension comprising suspending the particles provided in (i.1) in water, (i.3) Optionally, the particles of the aqueous suspension are Peak Particle Size a first peak having a value M1 and Peak Particle Size milling the aqueous suspension produced in (i.2) until it exhibits a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve including a second peak having a value M2, such that (M1 / μm):(M2 / μm)<1:1, such that (M2 / μm)<(M2' / μm) and / or (M1 / μm)<(M1' / μm). It is preferred that the compound contains
[0057] With regard to (i), it is preferred that (M2' / μm)-(M1' / μm)≧0.5, more preferably 0.5≦(M2' / μm)-(M1' / μm)≦30, more preferably 5≦(M2' / μm)-(M1' / μm)≦25, more preferably 10≦(M2' / μm)-(M1' / μm)≦23, and more preferably 15≦(M2' / μm)-(M1' / μm)≦20.
[0058] The particle size distribution of the mixed oxide particles provided in (i.1) is characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve being in the range of 0.5 to 7 micrometers. Peak Particle Size A first peak having a value M1' and a peak in the range of 8 to 60 micrometers Peak Particle Size Preferably, the method comprises grinding according to (i.3), which comprises a second peak having a value M2'.
[0059] The first peak of the particle size distribution curve of the mixed oxide particles provided in (i.1) is in the range of 1 to 5 micrometers, more preferably in the range of 1.5 to 4 micrometers, more preferably in the range of 1.75 to 3 micrometers. Peak Particle Size It is preferred that it has a value M1'.
[0060] The second peak of the particle size distribution curve of the mixed oxide particles provided in (i.1) is in the range of 10 to 40 micrometers, more preferably in the range of 12 to 30 micrometers, more preferably in the range of 15 to 25 micrometers. Peak Particle Size Preferably, the particle size distribution has a value M2' determined in accordance with Reference Example 1 herein.
[0061] The mixed oxide particles provided in (i.1) preferably have a Dv10 in the range of 0.2 to 10 micrometers, more preferably in the range of 0.5 to 7 micrometers, more preferably in the range of 0.6 to 4 micrometers, more preferably in the range of 0.75 to 3 micrometers, more preferably in the range of 0.9 to 1.75 micrometers, Dv10 being determined according to Reference Example 1 herein.
[0062] The mixed oxide particles provided in (i.1) have a Dv50 in the range of 1 to 30 micrometers, more preferably in the range of 1.5 to 20 micrometers, more preferably in the range of 1.75 to 10 micrometers, more preferably in the range of 2 to 5 micrometers, more preferably Dv50 determined according to Reference Example 1 herein.
[0063] Preferably, the mixed oxide particles provided in (i.1) have a Dv90 in the range of 5 to 45 micrometers, more preferably in the range of 8 to 40 micrometers, more preferably in the range of 12 to 30 micrometers, more preferably in the range of 15 to 25 micrometers, Dv90 being determined according to Reference Example 1 herein. More preferably, the mixed oxide particles provided in (i.1) have a Dv90 in the range of 17 to 24 micrometers, Dv90 being determined according to Reference Example 1 herein.
[0064] (ii) In the context of the present invention, with regard to (ii), it is preferred that the suspension obtained in (ii) has a solids content in the range of 25 to 55% by weight, more preferably in the range of 30 to 50% by weight, more preferably in the range of 35 to 45% by weight, relative to the weight of said suspension.
[0065] It is preferred that (ii) further comprises the step of adding a dispersant, the dispersant preferably being as defined above.
[0066] The particles of the oxide support in the suspension obtained according to (ii) have a Dv10 in the range of 0.3 to 4 micrometers, more preferably in the range of 0.4 to 3 micrometers, more preferably in the range of 0.5 to 2 micrometers, more preferably in the range of 0.55 to 1 micrometer, more preferably in the range of 0.6 to 0.8 micrometers, and Dv10 is preferably determined according to Reference Example 1 of the present specification.
[0067] The particles of the oxide support in the suspension obtained according to (ii) have a Dv50 in the range of 0.5 to 5 micrometers, more preferably in the range of 0.6 to 4 micrometers, more preferably in the range of 0.7 to 2 micrometers, more preferably in the range of 0.8 to 1.5 micrometers, the Dv50 being preferably determined according to Reference Example 1 of the present specification.
[0068] The particles of the oxide support in the suspension according to (ii) preferably have a Dv90 in the range of 0.5 to 6 micrometers, more preferably in the range of 1 to 4 micrometers, more preferably in the range of 1.5 to 3.5 micrometers, the Dv90 being determined according to Reference Example 1 herein. The particles of the oxide support in the suspension obtained according to (ii) preferably have a Dv90 in the range of 2 to 3 micrometers, the Dv90 being determined according to Reference Example 1 herein.
[0069] If the aqueous suspension obtained in (iii) does not contain particles of a mixed oxide comprising cerium, the particles of the oxide support in the suspension according to (ii) preferably exhibit a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 herein. If the aqueous suspension obtained in (iii) contains particles of a mixed oxide comprising cerium, the particles of the oxide support preferably exhibit a unimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 herein.
[0070] (iii) The suspension obtained in (iii) preferably has a solid content in the range of 25 to 55% by mass, more preferably in the range of 30 to 50% by mass, more preferably in the range of 35 to 45% by mass, based on the mass of the suspension.
[0071] It is preferred that (iii) further comprises the steps of measuring the pH of the aqueous phase of the suspension and adjusting the pH to a value in the range 4-9, more preferably in the range 5-8, more preferably in the range 6-7.
[0072] Preferably, (iii) further comprises the step of adding a source of oxidized binder, which source of oxidized binder is more preferably a source of oxidized binder as defined above.
[0073] After addition of the source of oxidized binder, the suspension of (iii) preferably has a solids content in the range of 25 to 55% by weight, more preferably in the range of 30 to 50% by weight, more preferably in the range of 35 to 45% by weight, relative to the weight of said suspension.
[0074] It is preferred that (iii) comprises the steps of measuring the pH of the aqueous phase of the obtained suspension after adding the source of oxidized binder and adjusting the pH to a value in the range from 4 to 9, more preferably in the range from 5 to 8, more preferably in the range from 6.5 to 7.5.
[0075] It is preferred that the method consists of (ii) and (iii), more preferably consists of (i), (ii) and (iii).
[0076] The present invention provides a method for producing a selective catalytic reduction catalyst, comprising the steps of: (a) producing an aqueous suspension according to the invention, preferably according to a method according to the invention, (b) disposing the suspension obtained in (a) on a surface of an interior wall of a substrate comprising a plurality of passageways defined by an inlet end, an outlet end, an axial length of the substrate extending between the inlet end and the outlet end, and an interior wall of the substrate extending therethrough, wherein an interface between the passageways and the interior wall is defined by a surface of the interior wall, and optionally drying the substrate with the suspension disposed thereon; (c) calcining the substrate obtained in (b). The present invention further relates to a method comprising the steps of:
[0077] The step of disposing the suspension according to (b) is preferably carried out by spraying the suspension onto the substrate or by immersing the substrate in the suspension, more preferably by immersing the substrate in the suspension.
[0078] The aqueous suspension obtained in (a) is disposed according to (b) over x% of the axial length of the substrate from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate, where x is preferably in the range of 80 to 100, more preferably in the range of 90 to 100, more preferably in the range of 95 to 100, and more preferably in the range of 98 to 100.
[0079] It is preferred that the (b) substrate is a flow-through substrate, more preferably one or more of a cordierite flow-through substrate and a silicon carbide flow-through substrate, more preferably a cordierite flow-through substrate. Alternatively, it is preferred that the (b) substrate is a wall-flow substrate, more preferably one or more of a cordierite wall-flow substrate and a silicon carbide wall-flow substrate, more preferably a cordierite wall-flow substrate. It is also contemplated that the substrate is a metal substrate. It is more preferred that the (b) substrate is a flow-through substrate, more preferably a cordierite flow-through substrate. It is more preferred that the inner wall of the (b) flow-through substrate has an average uncoated porosity in the range of 15-80%, more preferably in the range of 25-75%, more preferably in the range of 30-60%, more preferably the average porosity being determined according to Reference Example 4.
[0080] The drying step (b) is preferably carried out in a gas atmosphere having a temperature in the range of 60 to 180°C, more preferably in the range of 90 to 150°C, the gas atmosphere more preferably containing oxygen, and the gas atmosphere more preferably being air.
[0081] The drying step (b) is preferably carried out for a period in the range of 5 minutes to 3 hours, more preferably in the range of 10 minutes to 2 hours, more preferably in the range of 20 minutes to 1 hour.
[0082] Regarding (b), the placing step includes: (b.1) disposing a first portion of the aqueous suspension obtained in (a) on a surface of an interior wall of a substrate comprising an inlet end, an outlet end, an axial length of the substrate extending between the inlet end and the outlet end, and a plurality of passageways defined by the interior wall of the substrate extending therethrough, wherein an interface between the passageways and the interior wall is defined by the surface of the interior wall; and drying the substrate with the first portion of the suspension disposed thereon; (b.2) disposing a second portion of the aqueous suspension obtained in (a) onto the substrate obtained in (b.1) having the first portion of the suspension disposed thereon, and optionally drying the substrate having the first and second portions of the suspension disposed thereon; It is preferred that the compound contains
[0083] It is preferred that the first portion of the aqueous suspension obtained in (a) is positioned according to (b.1) over x1% of the axial length of the substrate from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate, where x1 is in the range of 80-100, more preferably in the range of 90-100, more preferably in the range of 95-100, more preferably in the range of 98-100.
[0084] It is preferred that the second portion of the aqueous suspension obtained in (a) is positioned according to (b.2) over x2% of the axial length of the substrate from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate, where x2 is in the range of 80-100, more preferably in the range of 90-100, more preferably in the range of 95-100, more preferably in the range of 98-100.
[0085] Preferably, the aqueous suspension obtained in (a) is disposed over x1% of the axial length of the substrate from the inlet end to the outlet end according to (b.1), and the second portion of the aqueous suspension obtained in (a) is disposed over x2% of the axial length of the substrate from the outlet end to the inlet end according to (b.2).
[0086] It is preferred that the drying step according to (b.1) is carried out in a gas atmosphere having a temperature in the range of 60 to 180°C, more preferably in the range of 90 to 150°C, the gas atmosphere more preferably comprising oxygen, the gas atmosphere more preferably being air.
[0087] The step of drying according to (b.1) is preferably carried out for a period in the range of 5 minutes to 3 hours, more preferably in the range of 10 minutes to 2 hours, more preferably in the range of 20 minutes to 1 hour.
[0088] With regard to (b.1), it is preferred that (b.1) further comprises a calcining step after drying, the calcining step being carried out in a gas atmosphere having a temperature in the range of 300 to 600°C, more preferably in the range of 350 to 550°C, more preferably in the range of 400 to 500°C, the gas atmosphere more preferably comprising oxygen, and the gas atmosphere is more preferably air.
[0089] With regard to (b.1), it is preferred that (b.1) further comprises a step of calcining after drying, wherein the calcining step is carried out in a gas atmosphere for a period in the range of 0.5 to 8 hours, more preferably in the range of 1 to 6 hours, more preferably in the range of 3 to 5 hours, wherein the gas atmosphere more preferably comprises oxygen, and wherein the gas atmosphere is more preferably air.
[0090] It is preferred that the drying step according to (b.2) is carried out in a gas atmosphere having a temperature in the range of 60 to 180°C, more preferably in the range of 90 to 150°C, the gas atmosphere more preferably comprising oxygen, the gas atmosphere more preferably being air.
[0091] The step of drying according to (b.2) is preferably carried out for a period in the range of from 5 minutes to 3 hours, more preferably in the range of from 10 minutes to 2 hours, more preferably in the range of from 20 minutes to 1 hour.
[0092] It is preferred that the calcination step according to (c) is carried out in a gas atmosphere having a temperature in the range of 300 to 600°C, more preferably in the range of 350 to 550°C, more preferably in the range of 400 to 500°C, the gas atmosphere more preferably comprising oxygen, the gas atmosphere more preferably being air.
[0093] It is preferred that the calcination step according to (c) is carried out in a gas atmosphere for a period in the range of from 0.5 to 8 hours, more preferably in the range of from 1 to 6 hours, more preferably in the range of from 3 to 5 hours, the gas atmosphere more preferably comprising oxygen, the gas atmosphere more preferably being air.
[0094] The present invention also relates to a selective catalytic reduction catalyst, preferably obtained or obtainable by the process according to the invention, a substrate including an inlet end, an outlet end, an axial length of the substrate extending between the inlet end and the outlet end, and a plurality of passages defined by an inner wall of the substrate extending therethrough, wherein interfaces between the passages and the inner wall are defined by a surface of the inner wall; A coating disposed on a surface of an interior wall of a substrate, the coating comprising a mixed oxide comprising one or more of vanadium oxide and tungsten oxide, and preferably cerium, supported on an oxide support. The present invention further relates to a catalyst comprising:
[0095] The coating comprises vanadium oxide supported on an oxide support, the vanadium oxide being preferably one or more of vanadium(V) oxide, vanadium(IV) oxide and vanadium(III) oxide.
[0096] The coating preferably contains vanadium oxide in an amount in the range of 1.5 to 10 mass %, more preferably in the range of 2.5 to 8 mass %, more preferably in the range of 3 to 5 mass %, based on the mass of the oxide support.
[0097] The oxide support comprises one or more of titanium, silicon, zirconium and tungsten, preferably one or more of titanium, silicon and tungsten, more preferably the oxide support comprises titania.More preferably the oxide support comprises titania and one or more of tungsten and silicon, more preferably tungsten or more preferably tungsten and silicon.
[0098] It is preferable that 95 to 100 mass%, more preferably 98 to 100 mass%, more preferably 99 to 100 mass%, more preferably 99.5 to 100 mass% of the oxide support is composed of titania and one or more of tungsten and silicon, more preferably tungsten or more preferably tungsten and silicon.
[0099] It is preferable that 70 to 99 mass%, more preferably 75 to 95 mass%, more preferably 80 to 90 mass%, and more preferably 85 to 90 mass% of the oxide support is made of titania. It is more preferable that 0.5 to 15 mass%, more preferably 3 to 15 mass%, and more preferably 6 to 12 mass% of the oxide support is made of tungsten calculated as WO3, and 0.5 to 15 mass%, more preferably 2 to 10 mass%, and more preferably 4 to 8 mass% of the oxide support is made of silicon calculated as SiO2.
[0100] The coating is carried out with an oxide carrier at a rate of 1.5 to 10 g / in 3 More preferably, the range is 2 to 7 g / in 3 More preferably, the range is 2.5 to 5 g / in 3 More preferably, the range is 2.5 to 4.2 g / in 3 It is preferred that the catalyst contains the fluorine atom at a loading in the range of 100 to 200 nm.
[0101] Preferably, the catalytic coating comprises a mixed oxide comprising cerium, the mixed oxide further comprising one or more of zirconium, niobium, molybdenum, lanthanum, yttrium, neodymium, praseodymium and hafnium, more preferably one or more of zirconium, lanthanum, praseodymium, yttrium and hafnium, more preferably one or more of zirconium, praseodymium, lanthanum and hafnium. More preferably, the mixed oxide further comprises zirconium, praseodymium, lanthanum and hafnium.
[0102] 20-60% by weight, more preferably 30-50% by weight, more preferably 35-45% by weight of the mixed oxide is composed of cerium calculated as CeO2, and 40-80% by weight, more preferably 50-70% by weight, more preferably 55-65% by weight of the mixed oxide is composed of ZrO2, Pr6O 11 , zirconium, praseodymium, lanthanum and hafnium calculated as La2O3 and HfO2, more preferably 30 to 60% by weight, more preferably 40 to 55% by weight, more preferably 45 to 55% by weight of the mixed oxide consists of zirconium calculated as ZrO2.
[0103] It is preferred that 95 to 100% by mass, more preferably 98 to 100% by mass, more preferably 99 to 100% by mass, and even more preferably 99.5 to 100% by mass of the mixed oxide consists of cerium, oxygen, zirconium, praseodymium, lanthanum and hafnium.
[0104] The coating is a mixture of oxides at 0.4 to 2.5 g / in 3 More preferably, the range is 0.6 to 2 g / in 3 More preferably, the range is 0.7 to 1.5 g / in 3 It is preferred that the catalyst contains the fluorine atom at a loading in the range of 100 to 200 nm.
[0105] The coating comprises a loading of mixed oxide (l1) and a loading of oxide support (l2), the loading ratio of mixed oxide to oxide support (l1):(l2) being preferably in the range of 1:1 to 1:10, more preferably in the range of 1:1.5 to 1:8, more preferably in the range of 1:2 to 1:7, more preferably in the range of 1:2.5 to 1:5.
[0106] The coating further comprises an oxidized binder, more preferably selected from the group consisting of alumina, silica, zirconia and mixtures of two or more thereof, more preferably selected from the group consisting of alumina, silica and mixtures of two or more thereof, more preferably silica. More preferably, the coating comprises a mixed oxide at a loading l1 (l1) and an oxidized binder at a loading l3 (l3), the loading ratio of the mixed oxide to the oxidized binder (l1):(l3) being in the range of 3.5:1 to 15:1, more preferably in the range of 4:1 to 10:1, more preferably in the range of 5:1 to 8:1.
[0107] The coating is applied with 0.05 to 0.5 g / in of oxidized binder. 3 More preferably, the range is 0.07 to 0.3 g / in 3 More preferably, the range is 0.08 to 0.25 g / in 3 It is preferred that the catalyst contains the fluorine atom at a loading in the range of 100 to 200 nm.
[0108] The catalyst is coated at 2.5 to 12 g / in 3 More preferably, the range is 3 to 8 g / in 3 More preferably, the range is 3.5 to 6 g / in 3 More preferably, in the range of 4 to 5.5 g / in 3 It is preferable that the content is in the range of 100 to 200 μg / kg.
[0109] It is preferred that 0-0.1 wt. %, more preferably 0-0.01 wt. %, more preferably 0-0.001 wt. % of the coating consists of zeolitic material, more preferably molecular sieves. It is to be understood that in the context of the present invention it is preferred that the coating is substantially free, more preferably free of zeolitic material, more preferably molecular sieves.
[0110] It is preferred that 0-0.01% by weight, more preferably 0-0.001% by weight, more preferably 0-0.0001% by weight, more preferably 0.00001% by weight of the coating consists of copper, more preferably copper and iron. It is to be understood that in the context of the present invention it is preferred that the coating is substantially free, more preferably free of copper, more preferably copper and iron.
[0111] It is preferred that 0-0.01% by weight, more preferably 0-0.001% by weight, more preferably 0-0.0001% by weight, more preferably 0.00001% by weight of the coating consists of platinum, more preferably platinum and palladium, more preferably platinum, palladium and rhodium, more preferably platinum group metals. In the context of the present invention, it is to be understood that it is preferred that the coating is substantially free, more preferably free, of platinum, more preferably platinum and palladium, more preferably platinum, palladium and rhodium. It is more preferred that the coating is substantially free, more preferably free, of platinum group metals.
[0112] It is preferred that 95-100% by weight, more preferably 98-100% by weight, more preferably 99-100% by weight, more preferably 99.5-100% by weight of the coating consists of a mixed oxide comprising one or more of vanadium oxide and tungsten oxide, and more preferably cerium, supported on an oxide support, as defined above, and more preferably an oxide binder.
[0113] It is preferred that the coating extends over x% of the axial length of the substrate on the surface of the inner wall from the inlet end to the outlet end or from the outlet end to the inlet end, where x is in the range 90-100, more preferably in the range 95-100, more preferably in the range 98-100.
[0114] It is preferred that the substrate is a flow-through substrate, more preferably one or more of a cordierite flow-through substrate and a silicon carbide flow-through substrate, more preferably a cordierite flow-through substrate. Alternatively, it is preferred that the substrate is a wall-flow substrate, more preferably one or more of a cordierite wall-flow substrate and a silicon carbide wall-flow substrate, more preferably a cordierite wall-flow substrate. It is also contemplated that the substrate is a metal substrate. It is more preferred that the substrate is a flow-through substrate, more preferably a cordierite flow-through substrate.
[0115] The catalyst of the present invention preferably comprises a substrate and a coating.
[0116] The present invention further relates to the use of the selective catalytic reduction catalyst according to the invention for the selective catalytic reduction of nitrogen oxides.
[0117] The present invention further relates to the use of the aqueous suspension according to the invention for producing a catalyst, more preferably a selective catalytic reduction catalyst.
[0118] The present invention relates to a method for selective catalytic reduction of nitrogen oxides, comprising the steps of: (1) providing an exhaust gas stream from a diesel engine, the exhaust gas stream including NOx; (2) passing the exhaust gas stream provided in (1) through selective catalytic reduction according to the present invention. The present invention further relates to a method comprising the steps of:
[0119] The present invention further relates to a method for improving the adhesion of a catalytic coating to a substrate, the method comprising using an aqueous suspension according to the invention to produce a catalyst, the catalyst being preferably a selective catalytic reduction catalyst.
[0120] The present invention is further illustrated by the following set of embodiments and combinations of embodiments, which are made up of dependencies and back references as indicated. In particular, it is to be noted that in each case where the scope of the embodiments is described in the context of the term, for example, "aqueous suspension according to any one of the embodiments 1 to 3", all the embodiments in this scope are intended to be expressly disclosed to the skilled person, i.e., the expression of this term is understood by the skilled person to be synonymous with "aqueous suspension according to any one of the embodiments 1, 2 and 3". Furthermore, it is to be expressly noted that the following set of embodiments represents a properly structured portion of the description directed to the general and preferred aspects of the present invention, rather than a set of claims determining the scope of protection.
[0121] 1. An aqueous suspension comprising water, one or more sources of vanadium oxide and tungsten oxide, and particles of an oxide support, The particles of the aqueous suspension exhibit a multimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve being in the range of 0.5 to 15 micrometers. Peak Particle Size A first peak having a value M(I) and a peak in the range of 1 to 40 micrometers Peak Particle Size an aqueous suspension comprising a second peak having a value M(II), wherein (M(I) / μm):(M(II) / μm)<1:1.
[0122] 2. A suspension as described in embodiment 1, wherein the particles of the aqueous suspension exhibit a bimodal particle size distribution.
[0123] 3. The suspension according to embodiment 1 or 2, further comprising particles of a mixed oxide comprising cerium.
[0124] 4. The mixed oxide further comprises one or more of zirconium, niobium, molybdenum, lanthanum, yttrium, neodymium, praseodymium and hafnium, preferably one or more of zirconium, lanthanum, praseodymium, yttrium and hafnium, more preferably one or more of zirconium, praseodymium, lanthanum and hafnium, more preferably the mixed oxide further comprises zirconium, praseodymium, lanthanum and hafnium; More preferably, 20 to 60% by mass, more preferably 30 to 50% by mass, more preferably 35 to 45% by mass of the mixed oxide consists of cerium calculated as CeO2, and more preferably 40 to 80% by mass, more preferably 50 to 70% by mass, more preferably 55 to 65% by mass of the mixed oxide consists of ZrO2, Pr6O 11 , composed of zirconium, praseodymium, lanthanum, and hafnium calculated as La2O3 and HfO2 、 More preferably, 30 to 60% by weight, more preferably 40 to 55% by weight, more preferably 45 to 55% by weight of the mixed oxide is zirconium calculated as ZrO2; 4. The suspension according to embodiment 3, wherein the mixed oxides consist of cerium, oxygen, zirconium, praseodymium, lanthanum and hafnium in an amount of more preferably 95 to 100% by weight, more preferably 98 to 100% by weight, more preferably 99 to 100% by weight, more preferably 99.5 to 100% by weight.
[0125] 5. The suspension according to embodiment 3 or 4, wherein the aqueous suspension comprises the mixed oxide in an amount ranging from 10 to 50% by weight, preferably from 20 to 45% by weight, more preferably from 25 to 40% by weight, more preferably from 25 to 35% by weight, relative to the weight of the oxide support.
[0126] 6. A suspension according to any one of embodiments 3 to 5, wherein the mixed oxide particles exhibit a unimodal or multimodal particle size distribution, preferably a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 herein.
[0127] 7. The suspension according to any one of the preceding embodiments, wherein (M(II) / μm)-(M(I) / μm)≧0.5, preferably 0.5≦(M(II) / μm)-(M(I) / μm)≦20, more preferably 1.5≦(M(II) / μm)-(M(I) / μm)≦15, more preferably 3≦(M(II) / μm)-(M(I) / μm)≦12, more preferably 4≦(M(II) / μm)-(M(I) / μm)≦10.
[0128] 8. M(I) is in the range of 0.5 to 5 micrometers, preferably in the range of 0.7 to 4 micrometers, more preferably in the range of 0.8 to 3.5 micrometers, more preferably in the range of 0.9 to 3 micrometers, more preferably in the range of 1 to 2.5 micrometers, more preferably in the range of 1.25 to 2 micrometers; The suspension according to any one of embodiments 1 to 7, wherein M(II) is in the range of 5.5 to 40 micrometers, preferably in the range of 6 to 20 micrometers, more preferably in the range of 6.25 to 15 micrometers, more preferably in the range of 6.5 to 10 micrometers, more preferably in the range of 6.75 to 9 micrometers.
[0129] 9. The suspension according to any one of embodiments 1 to 8, wherein the particles of the aqueous suspension have a Dv10 in the range of 0.01 to 3 micrometers, preferably in the range of 0.1 to 2.5 micrometers, more preferably in the range of 0.25 to 2 micrometers, more preferably in the range of 0.4 to 1.5 micrometers, more preferably in the range of 0.5 to 1.25 micrometers, wherein Dv10 is determined according to Reference Example 1 herein.
[0130] 10. A suspension according to any one of embodiments 1 to 9, wherein the particles of the aqueous suspension have a Dv50 in the range of 0.2 to 10 micrometers, preferably in the range of 0.5 to 7 micrometers, more preferably in the range of 0.75 to 4 micrometers, more preferably in the range of 0.9 to 3 micrometers, more preferably in the range of 1 to 2.5 micrometers, wherein the Dv50 is determined according to Reference Example 1 herein.
[0131] 11. A suspension according to any one of embodiments 1 to 10, wherein the particles of the aqueous suspension have a Dv90 in the range of 1 to 30 micrometers, preferably in the range of 1.5 to 20 micrometers, more preferably in the range of 1.75 to 10 micrometers, more preferably in the range of 2 to 5 micrometers, more preferably in the range of 2 to 4 micrometers, wherein the Dv90 is determined according to Reference Example 1 herein.
[0132] 12. The suspension according to any one of embodiments 1 to 11, having a solids content in the range of 10 to 60% by mass, preferably in the range of 20 to 55% by mass, more preferably in the range of 30 to 50% by mass, more preferably in the range of 35 to 45% by mass, based on the mass of the aqueous suspension.
[0133] 13. The suspension according to any one of embodiments 1 to 12, having a pH in the range of 2 to 12, preferably in the range of 3 to 10, more preferably in the range of 4 to 9, more preferably in the range of 5 to 8, more preferably in the range of 6 to 7.5.
[0134] 14. 20-200mPa measured at 300 revolutions per second * s range, preferably 50 to 100 mPa * 14. The suspension according to any one of the preceding embodiments, having a viscosity in the range of s.
[0135] 15. The suspension of any one of the preceding embodiments, wherein the aqueous suspension comprises a source of vanadium oxide, the source of vanadium oxide being preferably selected from the group consisting of a vanadium oxalate solution, ammonium metavanadate, and mixtures of two or more thereof, more preferably a vanadium oxalate solution.
[0136] 16. The suspension according to any one of the preceding embodiments, wherein the aqueous suspension comprises a source of vanadium oxide, calculated as V2O5, in an amount in the range of 1.5 to 8% by weight, preferably in the range of 2 to 7% by weight, more preferably in the range of 3 to 6% by weight, relative to the weight of the oxide support.
[0137] 17. The particles of the oxide support exhibit a monomodal particle size distribution characterized by a particle size distribution curve determined in accordance with Reference Example 1 of the present specification, or 17. The suspension according to any one of the preceding embodiments, wherein the particles of the oxide support exhibit a multimodal particle size distribution, preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 herein.
[0138] 18. The suspension of any one of the preceding embodiments, wherein the oxide support comprises one or more of titanium, silicon, zirconium, and tungsten, preferably one or more of titanium, silicon and zirconium, more preferably one or more of titanium, silicon and tungsten, more preferably titania, and more preferably one or more of tungsten and silicon, more preferably tungsten or more preferably tungsten and silicon.
[0139] 19. The suspension according to embodiment 18, wherein 95 to 100% by weight, preferably 98 to 100% by weight, more preferably 99 to 100% by weight, more preferably 99.5 to 100% by weight of the oxide support consists of titania and preferably one or more of tungsten and silicon, more preferably tungsten or more preferably tungsten and silicon.
[0140] 20. 70 to 99 mass%, preferably 75 to 95 mass%, more preferably 80 to 90 mass%, and more preferably 85 to 90 mass% of the oxide support is made of titania; 0.5 to 15 mass %, preferably 3 to 15 mass %, more preferably 6 to 12 mass % of the oxide support is made of tungsten calculated as WO3; 20. The suspension according to embodiment 19, wherein 0.5 to 15% by weight, preferably 2 to 10% by weight, more preferably 4 to 8% by weight of the oxide support consists of silicon calculated as SiO2.
[0141] 21. The suspension according to any one of the preceding embodiments, wherein 40 to 90% by mass, preferably 50 to 85% by mass, more preferably 55 to 80% by mass of the aqueous suspension consists of water.
[0142] 22. The suspension of any one of the preceding embodiments, wherein the aqueous suspension further comprises an acid, preferably an organic acid, preferably selected from the group consisting of acetic acid, tartaric acid, formic acid, lactic acid, oxalic acid and mixtures of two or more thereof, more preferably selected from the group consisting of acetic acid, tartaric acid, formic acid, oxalic acid and mixtures of two or more thereof, more preferably selected from the group consisting of acetic acid, tartaric acid and mixtures of two or more thereof, more preferably the organic acid is tartaric acid.
[0143] 23. The suspension of any one of the preceding embodiments, wherein the aqueous suspension further comprises one or more dispersants, which are preferably organic polymers, which are preferably acrylic polymers.
[0144] 24. The suspension of any one of the preceding embodiments, wherein the aqueous suspension further comprises a source of oxidized binder, the oxidized binder is preferably selected from the group consisting of alumina, silica, zirconia, and mixtures of two or more thereof, more preferably selected from the group consisting of alumina, silica, and mixtures of two or more thereof, more preferably silica, and the source of oxidized binder is more preferably colloidal silica.
[0145] 25. The suspension according to any one of the preceding embodiments, wherein 0-0.1% by weight, preferably 0-0.01% by weight, more preferably 0-0.001% by weight of the aqueous suspension consists of zeolitic material, preferably molecular sieves.
[0146] 26. The suspension according to any one of the preceding embodiments, wherein the aqueous suspension preferably comprises 0-0.01% by mass, more preferably 0-0.001% by mass, more preferably 0-0.0001% by mass of copper, preferably copper and iron.
[0147] 27. The suspension according to any one of embodiments 1 to 26, wherein the aqueous suspension comprises 0 to 0.01% by mass, preferably 0 to 0.001% by mass, more preferably 0 to 0.0001% by mass, more preferably 0 to 0.00001% by mass of platinum, preferably platinum and palladium, more preferably platinum, palladium and rhodium, more preferably platinum group metals.
[0148] 28. A 98-100% by weight, preferably 99-100% by weight, more preferably 99.5-100% by weight, aqueous suspension consisting of water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, one or more acids, preferably as defined in embodiment 22, a dispersant as defined in embodiment 23 and a source of an oxide binder as defined in embodiment 24, 3. The suspension according to embodiment 1 or 2, wherein the aqueous suspension more preferably consists of water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, more preferably one or more of an acid as defined in embodiment 22, a dispersant as defined in embodiment 23 and a source of an oxide binder as defined in embodiment 24.
[0149] 29. A 98-100% by weight, preferably 99-100% by weight, more preferably 99.5-100% by weight, aqueous suspension comprising water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, particles of a mixed oxide comprising cerium as defined in any one of embodiments 3 to 6, one or more acids, preferably as defined in embodiment 22, a source of a dispersing agent as defined in embodiment 23 and an oxidized binder as defined in embodiment 24, more preferably an acid as defined in embodiment 22, a dispersing agent as defined in embodiment 23 and a source of an oxidized binder as defined in embodiment 24, 28. The suspension according to any one of the preceding embodiments, wherein the aqueous suspension more preferably consists of water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, particles of a mixed oxide comprising cerium as defined in any one of the preceding embodiments 3 to 6, more preferably one or more of an acid as defined in embodiment 22, a dispersing agent as defined in embodiment 23 and a source of an oxidized binder as defined in embodiment 24, more preferably an acid as defined in embodiment 22, a dispersing agent as defined in embodiment 23 and a source of an oxidized binder as defined in embodiment 24.
[0150] 30. (i) optionally producing an aqueous suspension comprising water and particles of a mixed oxide comprising cerium, said mixed oxide preferably being a mixed oxide as defined in any one of embodiments 4 to 6, and wherein the particles of the mixed oxide contained in said aqueous suspension exhibit a monomodal particle size distribution; or Optionally, producing an aqueous suspension comprising water and particles of a mixed oxide comprising cerium, said mixed oxide preferably as defined in any one of embodiments 4 to 6, and wherein the mixed oxide particles contained in said aqueous suspension exhibit a multimodal, preferably bimodal, particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein, said particle size distribution curve comprising a first peak having a maximum value M1 in the range of 0.5 to 20 micrometers and a second peak having a maximum value M2 in the range of 1 to 50 micrometers, wherein (M1 / μm):(M2 / μm)<1:1, (ii) producing an aqueous suspension comprising water and one or more sources of vanadium oxide and tungsten oxide, said one or more sources of vanadium oxide and tungsten oxide being preferably one or more sources of vanadium oxide and tungsten oxide as defined in embodiment 15, and further comprising oxide support particles, wherein the oxide support particles contained in the aqueous suspension exhibit a unimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein, said particle size distribution curve comprising a peak having a maximum value in the range of 0.5 to 5 micrometers, preferably in the range of 0.7 to 4 micrometers, more preferably in the range of 0.8 to 3.5 micrometers, more preferably in the range of 0.9 to 3 micrometers, more preferably in the range of 1 to 2.5 micrometers, more preferably in the range of 1.25 to 2 micrometers, or the oxide support particles contained in the aqueous suspension exhibit a multimodal particle size distribution, more preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 herein, (iii) mixing the suspension from (ii) optionally with the suspension from (i) to obtain an aqueous suspension comprising water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, and optionally particles of a mixed oxide comprising cerium, wherein the particles of the aqueous suspension exhibit a multimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein, said particle size distribution curve comprising a first peak having a maximum value M(I) in the range of 0.5 to 15 micrometers and a second peak having a maximum value M(II) in the range of 1 to 40 micrometers, wherein (M(I) / μm):(M(II) / μm)<1:1. 30. A method for producing an aqueous suspension according to any one of the preceding embodiments, comprising:
[0151] 31. The method according to embodiment 30, wherein the suspension obtained in (i) has a solids content in the range of 20 to 50% by weight, preferably in the range of 25 to 45% by weight, more preferably in the range of 30 to 40% by weight, relative to the weight of the suspension.
[0152] 32. The method of embodiment 30 or 31, wherein (i) further comprises the step of adding an acid, the acid being preferably an acid as defined in embodiment 23.
[0153] 33. The method according to any one of embodiments 30 to 32, wherein (M2 / μm)-(M1 / μm)≧0.5, preferably 0.5≦(M2 / μm)-(M1 / μm)≦30, more preferably 5≦(M2 / μm)-(M1 / μm)≦25, more preferably 10≦(M2 / μm)-(M1 / μm)≦23, more preferably 13≦(M2 / μm)-(M1 / μm)≦19.
[0154] 34. The particle size distribution of the aqueous suspension obtained according to (i) is characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, and the particle size distribution curve is in the range of 0.5 to 8 micrometers. Peak Particle Size A first peak having a value M1 and a peak in the range of 9 to 50 micrometers Peak Particle Size34. The method of any one of embodiments 30 to 33, comprising a second peak having a value M2.
[0155] 35. The method according to any one of embodiments 30 to 34, wherein according to (i), M1 is in the range of 1.25 to 6 micrometers, preferably in the range of 1.75 to 4 micrometers, more preferably in the range of 1.85 to 3 micrometers, and M2 is in the range of 9 to 35 micrometers, more preferably in the range of 10 to 25 micrometers, more preferably in the range of 12 to 25 micrometers.
[0156] 36. The method according to any one of embodiments 30 to 35, wherein the particles of the suspension obtained according to (i) have a Dv10 in the range of 0.2 to 8 micrometers, preferably in the range of 0.45 to 5 micrometers, more preferably in the range of 0.5 to 4 micrometers, more preferably in the range of 0.6 to 2.5 micrometers, more preferably in the range of 0.8 to 1.25 micrometers, wherein Dv10 is determined according to Reference Example 1 herein.
[0157] 37. The method according to any one of embodiments 30 to 36, wherein the particles of the suspension obtained according to (i) have a Dv50 in the range of 1 to 25 micrometers, preferably in the range of 1.5 to 10 micrometers, more preferably in the range of 1.75 to 7 micrometers, more preferably in the range of 2 to 4 micrometers, wherein Dv50 is determined according to Reference Example 1 herein.
[0158] 38. The method according to any one of embodiments 30 to 37, wherein the particles of the suspension obtained according to (i) have a Dv90 in the range of 3 to 30 micrometers, preferably in the range of 6 to 25 micrometers, more preferably in the range of 8 to 20 micrometers, more preferably in the range of 10 to 18 micrometers, more preferably in the range of 12 to 16 micrometers, wherein Dv90 is determined according to Reference Example 1 herein.
[0159] 39. The process for producing an aqueous suspension according to (i) comprises: (i.1') a step of providing particles of a mixed oxide comprising cerium, the mixed oxide particles exhibiting a monomodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve comprising a peak having a maximum value in the range of 5.5 to 40 micrometers, preferably in the range of 6 to 20 micrometers, more preferably in the range of 6.25 to 15 micrometers, more preferably in the range of 6.5 to 10 micrometers, more preferably in the range of 6.75 to 9 micrometers, (i.2') preparing an aqueous suspension comprising suspending the particles provided in (i.1') in water. 39. The method of any one of embodiments 30 to 38, comprising:
[0160] 40. The process for producing an aqueous suspension according to (i) comprises: (i.1) a step of providing particles of a mixed oxide comprising cerium, the mixed oxide particles exhibiting a multimodal particle size distribution, preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve being in the range of 0.5 to 30 micrometers Peak Particle Size A first peak having a value M1' and a peak in the range of 1 to 60 micrometers Peak Particle Size a second peak having a value M2', where (M1' / μm):(M2' / μm)<1:1; (i.2) preparing an aqueous suspension comprising suspending the particles provided in (i.1) in water, (i.3) optionally milling the aqueous suspension produced in (i.2) until the particles of the aqueous suspension exhibit a multimodal particle size distribution, preferably a bimodal particle size distribution, characterized by a particle size distribution curve determined according to Reference Example 1 herein, said particle size distribution curve being: Peak Particle Size a first peak having a value M1 and Peak Particle Size a second peak having a value M2, where (M1 / μm):(M2 / μm)<1:1, where (M2 / μm)<(M2' / μm) and / or (M1 / μm)<(M1' / μm); 39. The method of any one of embodiments 30 to 38, comprising:
[0161] 41. The method according to embodiment 40, wherein (M2' / μm)-(M1' / μm)≧0.5, preferably 0.5≦(M2' / μm)-(M1' / μm)≦30, more preferably 5≦(M2' / μm)-(M1' / μm)≦25, more preferably 10≦(M2' / μm)-(M1' / μm)≦23, more preferably 15≦(M2' / μm)-(M1' / μm)≦20.
[0162] 42. The particle size distribution of the mixed oxide particles provided in (i.1) is characterized by a particle size distribution curve determined according to Reference Example 1 of the present specification, said particle size distribution curve being in the range of 0.5 to 7 micrometers. Peak Particle Size A first peak having a value M1' and a peak in the range of 8 to 60 micrometers Peak Particle Size 42. The method of embodiment 40 or 41, wherein the second peak has a value M2′ and the method comprises grinding according to (i.3).
[0163] 43. The mixed oxide particles provided in (i.1) have a first peak in the particle size distribution curve in the range of 1 to 5 micrometers, preferably in the range of 1.5 to 4 micrometers, more preferably in the range of 1.75 to 3 micrometers. Peak Particle Size 43. The method of any one of embodiments 40 to 42, having a value M1'.
[0164] 44. The mixed oxide particles provided in (i.1) have a second peak in the particle size distribution curve in the range of 10 to 40 micrometers, preferably in the range of 12 to 30 micrometers, more preferably in the range of 15 to 25 micrometers. Peak Particle Size The method according to any one of embodiments 40 to 43, wherein the particle size distribution has a value M2' and is determined according to Example 1 herein.
[0165] 45. The method according to any one of embodiments 40 to 44, wherein the particles of the mixed oxide provided in (i.1) have a Dv10 in the range of 0.2 to 10 micrometers, preferably in the range of 0.5 to 7 micrometers, more preferably in the range of 0.6 to 4 micrometers, more preferably in the range of 0.75 to 3 micrometers, more preferably in the range of 0.9 to 1.75 micrometers, wherein Dv10 is determined according to Reference Example 1 herein.
[0166] 46. The method according to any one of embodiments 40 to 45, wherein the particles of the mixed oxide provided in (i.1) have a Dv50 in the range of 1 to 30 micrometers, preferably in the range of 1.5 to 20 micrometers, more preferably in the range of 1.75 to 10 micrometers, more preferably in the range of 2 to 5 micrometers, wherein Dv50 is determined according to Reference Example 1 herein.
[0167] 47. The method according to any one of embodiments 40 to 46, wherein the particles of the mixed oxide provided in (i.1) have a Dv90 in the range of 5 to 45 micrometers, preferably in the range of 8 to 40 micrometers, more preferably in the range of 12 to 30 micrometers, more preferably in the range of 15 to 25 micrometers, wherein Dv90 is determined according to Reference Example 1 herein.
[0168] 48. The method according to embodiment 47, wherein the particles of the mixed oxide provided in (i.1) have a Dv90 in the range of 17 to 24 micrometers, the Dv90 being determined according to Reference Example 1 herein.
[0169] 49. The method according to any one of embodiments 30 to 48, wherein the suspension obtained in (ii) has a solids content in the range of 25 to 55% by weight, preferably in the range of 30 to 50% by weight, more preferably in the range of 35 to 45% by weight, relative to the weight of the suspension.
[0170] 50. The method of any one of embodiments 30 to 49, wherein (ii) further comprises the step of adding a dispersant, the dispersant being preferably as defined in embodiment 24.
[0171] 51. The method according to any one of embodiments 30 to 50, wherein the particles of the oxide support in the suspension obtained according to (ii) have a Dv10 in the range of 0.3 to 4 micrometers, preferably in the range of 0.4 to 3 micrometers, more preferably in the range of 0.5 to 2 micrometers, more preferably in the range of 0.55 to 1 micrometer, more preferably in the range of 0.6 to 0.8 micrometers, wherein Dv10 is determined according to Reference Example 1 herein.
[0172] 52. The method according to any one of embodiments 30 to 51, wherein the particles of the oxide support in the suspension obtained according to (ii) have a Dv50 in the range of 0.5 to 5 micrometers, preferably in the range of 0.6 to 4 micrometers, more preferably in the range of 0.7 to 2 micrometers, more preferably in the range of 0.8 to 1.5 micrometers, wherein Dv50 is determined according to Reference Example 1 herein.
[0173] 53. The method according to any one of embodiments 30 to 52, wherein the particles of the oxide support in the suspension according to (ii) have a Dv90 in the range of 0.5 to 6 micrometers, preferably in the range of 1 to 4 micrometers, more preferably in the range of 1.5 to 3.5 micrometers, wherein Dv90 is determined according to Reference Example 1 herein.
[0174] 54. The method according to embodiment 53, wherein the particles of the oxide support in the suspension obtained according to (ii) have a Dv90 in the range of 2 to 3 micrometers, the Dv90 being determined according to Reference Example 1 herein.
[0175] 55. The method according to any one of embodiments 30 to 54, wherein the suspension obtained in (iii) has a solids content in the range of 25 to 55% by weight, preferably in the range of 30 to 50% by weight, more preferably in the range of 35 to 45% by weight, based on the weight of the suspension.
[0176] 56. The method according to any one of embodiments 30 to 55, wherein (iii) further comprises the steps of measuring the pH of the aqueous phase of the suspension and adjusting the pH to a value in the range of 4 to 9, preferably in the range of 5 to 8, more preferably in the range of 6 to 7.
[0177] 57. The method of any one of embodiments 30 to 56, wherein (iii) further comprises the step of adding a source of oxidized binder, the source of oxidized binder being preferably a source of oxidized binder as defined in embodiment 25.
[0178] 58. The method of embodiment 57, wherein after adding the source of oxidized binder, the suspension of (iii) has a solids content in the range of 25 to 55% by weight, preferably in the range of 30 to 50% by weight, more preferably in the range of 35 to 45% by weight, based on the weight of the suspension.
[0179] 59. The method according to embodiment 57 or 58, wherein (iii) comprises the steps of measuring the pH of the aqueous phase of the obtained suspension after adding the source of oxidized binder, and adjusting the pH to a value in the range from 4 to 9, preferably in the range from 5 to 8, more preferably in the range from 6.5 to 7.5.
[0180] 60. The method according to any one of embodiments 30 to 59, consisting of (ii) and (iii), preferably (i), (ii) and (iii).
[0181] 61. A method for producing a selective catalytic reduction catalyst, comprising: (a) producing an aqueous suspension according to any one of embodiments 1 to 29, preferably according to a method according to any one of embodiments 30 to 60, (b) disposing the suspension obtained in (a) on a surface of an interior wall of a substrate comprising an inlet end, an outlet end, an axial length of the substrate extending between the inlet end and the outlet end, and a plurality of passageways defined by the interior wall of the substrate extending therethrough, wherein an interface between the passageways and the interior wall is defined by the surface of the interior wall, and optionally drying the substrate with the suspension disposed thereon; (c) calcining the substrate obtained in (b). A method comprising:
[0182] 62. The method according to embodiment 61, wherein the step of disposing the suspension according to (b) is carried out by spraying the suspension onto the substrate or by immersing the substrate in the suspension, preferably by immersing the substrate in the suspension.
[0183] 63. The method according to embodiment 61 or 62, wherein the aqueous suspension obtained in (a) is disposed according to (b) over x% of the axial length of the substrate from the inlet end to the outlet end or from the outlet end to the inlet end of the substrate, where x is in the range of 80 to 100, preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100.
[0184] 64. The substrate of (b) is a flow-through substrate, preferably one or more of a cordierite flow-through substrate and a silicon carbide flow-through substrate, more preferably a cordierite flow-through substrate; or (b) the substrate is a wall-flow substrate, preferably one or more of a cordierite wall-flow substrate and a silicon carbide wall-flow substrate, more preferably a cordierite wall-flow substrate; The substrate of (b) is preferably a flow-through substrate, more preferably a cordierite flow-through substrate; The method according to any one of embodiments 61 to 63, wherein the inner wall of the flow-through substrate (b) has an average uncoated porosity, more preferably in the range of 15 to 80%, more preferably in the range of 25 to 75%, more preferably in the range of 30 to 60%, the average porosity being determined according to Reference Example 4.
[0185] 65. The drying step (b) is carried out in a gas atmosphere having a temperature in the range of 60 to 180°C, preferably in the range of 90 to 150°C, the gas atmosphere preferably containing oxygen, and the gas atmosphere is more preferably air; The method according to any one of embodiments 61 to 64, wherein the drying step (b) is carried out for a period preferably in the range of 5 minutes to 3 hours, more preferably in the range of 10 minutes to 2 hours, more preferably in the range of 20 minutes to 1 hour.
[0186] 66. The step of placing according to (b) (b.1) disposing a first portion of the aqueous suspension obtained in (a) on a surface of an interior wall of a substrate comprising an inlet end, an outlet end, an axial length of the substrate extending between the inlet end and the outlet end, and a plurality of passageways defined by the interior wall of the substrate extending therethrough, wherein an interface between the passageways and the interior wall is defined by the surface of the interior wall; and drying the substrate with the first portion of the suspension disposed thereon; (b.2) disposing a second portion of the aqueous suspension obtained in (a) onto the substrate obtained in (b.1) having the first portion of the suspension disposed thereon, and optionally drying the substrate having the first and second portions of the suspension disposed thereon. 66. The method of any one of embodiments 61 to 65, comprising:
[0187] 67. The method according to embodiment 66, wherein the first portion of the aqueous suspension obtained in (a) is disposed over x1% of the axial length of the substrate from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate according to (b.1), where x1 is in the range of 80 to 100, preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100.
[0188] 68. The method according to embodiment 66 or 67, wherein the second portion of the aqueous suspension obtained in (a) is disposed according to (b.2) over x2% of the axial length of the substrate from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate, where x2 is in the range of 80 to 100, preferably in the range of 90 to 100, more preferably in the range of 95 to 100, more preferably in the range of 98 to 100.
[0189] 69. The method of embodiment 67 or 68, wherein a first portion of the aqueous suspension obtained in (a) is disposed over x1% of the axial length of the substrate from the inlet end to the outlet end according to (b.1), and a second portion of the aqueous suspension obtained in (a) is disposed over x2% of the axial length of the substrate from the outlet end to the inlet end according to (b.2).
[0190] 70. The step of drying according to (b.1) is carried out in a gas atmosphere having a temperature in the range of 60 to 180°C, preferably in the range of 90 to 150°C, the gas atmosphere preferably containing oxygen, more preferably the gas atmosphere is air, The method according to any one of embodiments 66 to 69, wherein the drying step according to (b.1) is preferably carried out for a period in the range of 5 minutes to 3 hours, more preferably in the range of 10 minutes to 2 hours, more preferably in the range of 20 minutes to 1 hour.
[0191] 71. The method according to any one of embodiments 66 to 70, wherein (b.1) further comprises, after drying, a calcination step carried out in a gas atmosphere having a temperature in the range of 300 to 600°C, preferably in the range of 350 to 550°C, more preferably in the range of 400 to 500°C, wherein the gas atmosphere preferably comprises oxygen, and more preferably the gas atmosphere is air.
[0192] 72. The method according to any one of embodiments 66 to 71, wherein (b.1) further comprises, after drying, a calcination step carried out in a gas atmosphere for a period in the range of 0.5 to 8 hours, preferably in the range of 1 to 6 hours, more preferably in the range of 3 to 5 hours, wherein the gas atmosphere preferably comprises oxygen, and wherein the gas atmosphere is more preferably air.
[0193] 73. The step of drying according to (b.2) is carried out in a gas atmosphere having a temperature in the range of 60 to 180°C, preferably in the range of 90 to 150°C, the gas atmosphere preferably containing oxygen, more preferably the gas atmosphere is air, The step of drying according to (b.2) is preferably carried out for a period ranging from 5 minutes to 3 hours, preferably ranging from 10 minutes to 2 hours, more preferably ranging from 20 minutes to 1 hour, 73. The method according to any one of embodiments 66 to 72.
[0194] 74. The method of any one of embodiments 61 to 73, wherein the calcination step according to (c) is carried out in a gas atmosphere having a temperature in the range of 300 to 600°C, preferably in the range of 350 to 550°C, more preferably in the range of 400 to 500°C, the gas atmosphere preferably comprising oxygen, and the gas atmosphere is more preferably air.
[0195] 75. The method of any one of embodiments 61 to 74, wherein the calcination step according to (c) is carried out in a gas atmosphere for a period in the range of 0.5 to 8 hours, preferably in the range of 1 to 6 hours, more preferably in the range of 3 to 5 hours, the gas atmosphere preferably comprising oxygen, and the gas atmosphere is more preferably air.
[0196] 76. A selective catalytic reduction catalyst, preferably obtained or obtainable by a method according to any one of embodiments 61 to 75, a substrate including an inlet end, an outlet end, an axial length of the substrate extending between the inlet end and the outlet end, and a plurality of passages defined by an inner wall of the substrate extending therethrough, wherein interfaces between the passages and the inner wall are defined by a surface of the inner wall; A coating disposed on a surface of an interior wall of a substrate, the coating comprising a mixed oxide comprising one or more of vanadium oxide and tungsten oxide, and preferably cerium, supported on an oxide support. A catalyst comprising:
[0197] 77. The catalyst of embodiment 76, wherein the coating comprises vanadium oxide supported on an oxide support, the vanadium oxide being one or more of vanadium(V) oxide, vanadium(IV) oxide, and vanadium(III) oxide.
[0198] 78. The catalyst of embodiment 76 or 77, wherein the coating comprises vanadium oxide in an amount in the range of 1.5 to 10% by weight, preferably in the range of 2.5 to 8% by weight, more preferably in the range of 3 to 5% by weight, based on the weight of the oxide support.
[0199] 79. The oxide support comprises one or more of titanium, silicon, zirconium and tungsten, preferably one or more of titanium, silicon and tungsten, more preferably the oxide support comprises titania; The oxide support more preferably comprises titania and one or more of tungsten and silicon, more preferably tungsten or more preferably tungsten and silicon; The catalyst of any one of embodiments 76 to 78.
[0200] 80. The catalyst of embodiment 79, wherein 95 to 100% by weight, preferably 98 to 100% by weight, more preferably 99 to 100% by weight, more preferably 99.5 to 100% by weight of the oxide support consists of titania, and preferably one or more of tungsten and silicon, more preferably tungsten or more preferably tungsten and silicon.
[0201] 81. 70 to 99 mass%, preferably 75 to 95 mass%, more preferably 80 to 90 mass%, more preferably 85 to 90 mass% of the oxide support is made of titania; 0.5 to 15 mass %, preferably 3 to 15 mass %, more preferably 6 to 12 mass % of the oxide support is made of tungsten calculated as WO3; Catalyst according to embodiment 80, wherein 0.5 to 15% by weight, preferably 2 to 10% by weight, more preferably 4 to 8% by weight of the oxide support consists of silicon calculated as SiO2.
[0202] 82. The coating is applied to the oxide support at a rate of 1.5 to 10 g / in 3 in the range of 2 to 7 g / in 3 More preferably, the range is 2.5 to 5 g / in 3 More preferably, the range is 2.5 to 4.2 g / in 3 82. The catalyst of any one of embodiments 76 to 81, comprising at a loading in the catalyst in the range of
[0203] 83. A catalytic coating comprising a mixed oxide comprising cerium, the mixed oxide further comprising one or more of zirconium, niobium, molybdenum, lanthanum, yttrium, neodymium, praseodymium and hafnium, preferably one or more of zirconium, lanthanum, praseodymium, yttrium and hafnium, more preferably one or more of zirconium, praseodymium, lanthanum and hafnium, the mixed oxide more preferably further comprising zirconium, praseodymium, lanthanum and hafnium; More preferably, 20 to 60% by mass, more preferably 30 to 50% by mass, more preferably 35 to 45% by mass of the mixed oxide consists of cerium calculated as CeO2, and more preferably 40 to 80% by mass, more preferably 50 to 70% by mass, more preferably 55 to 65% by mass of the mixed oxide consists of ZrO2, Pr6O 1183. The catalyst according to any one of embodiments 76 to 82, wherein the mixed oxides consist of zirconium, praseodymium, lanthanum and hafnium, calculated as La2O3 and HfO2, more preferably 30 to 60%, more preferably 40 to 55%, more preferably 45 to 55% by weight of the mixed oxides consist of zirconium, calculated as ZrO2.
[0204] 84. The catalyst according to any one of embodiments 76 to 83, wherein 95 to 100% by weight, preferably 98 to 100% by weight, more preferably 99 to 100% by weight, more preferably 99.5 to 100% by weight of the mixed oxides consists of cerium, oxygen, zirconium, praseodymium, lanthanum and hafnium.
[0205] 85. The coating is made of mixed oxides at 0.4-2.5 g / in 3 in the range of 0.6 to 2 g / in 3 More preferably, the range is 0.7 to 1.5 g / in 3 85. The catalyst of any one of embodiments 76 to 84, comprising a loading in the catalyst in the range of
[0206] 86. The catalyst according to any one of embodiments 76 to 85, wherein the coating comprises the mixed oxide in a loading l1 (l1) and the oxide support in a loading l2 (l2), and the loading ratio of the mixed oxide to the oxide support (l1):(l2) is in the range of 1:1 to 1:10, preferably in the range of 1:1.5 to 1:8, more preferably in the range of 1:2 to 1:7, more preferably in the range of 1:2.5 to 1:5.
[0207] 87. The catalyst of any one of embodiments 76 to 86, wherein the coating further comprises an oxidized binder, the oxidized binder being preferably selected from the group consisting of alumina, silica, zirconia, and mixtures of two or more thereof, more preferably selected from the group consisting of alumina, silica, and mixtures of two or more thereof, more preferably silica.
[0208] 88. The catalyst of embodiment 87, wherein the coating comprises a loading of the mixed oxide (l1) and a loading of the oxide binder (l3), and the loading ratio of the mixed oxide to the oxide binder (l1):(l3) is in the range of 3.5:1 to 15:1, preferably in the range of 4:1 to 10:1, more preferably in the range of 5:1 to 8:1.
[0209] 89. The coating contains 0.05-0.5 g / in2 of oxidized binder. 3 in the range of 0.07 to 0.3 g / in 3 More preferably, the range is 0.08 to 0.25 g / in 3 89. The catalyst of embodiment 87 or 88, comprising at a loading in the catalyst in the range of
[0210] 90. Coating: 2.5~12g / in 3 in the range of 3 to 8 g / in 3 More preferably, the range is 3.5 to 6 g / in 3 More preferably, in the range of 4 to 5.5 g / in 3 90. The catalyst of any one of embodiments 76 to 89, comprising a loading in the range of:
[0211] 91. The catalyst according to any one of embodiments 76 to 90, wherein 0 to 0.1 wt. %, preferably 0 to 0.01 wt. %, more preferably 0 to 0.001 wt. % of the coating consists of a zeolitic material, preferably a molecular sieve.
[0212] 92. The catalyst according to any one of embodiments 76 to 91, wherein 0 to 0.01% by weight, preferably 0 to 0.001% by weight, more preferably 0 to 0.0001% by weight of the coating consists of copper, preferably copper and iron.
[0213] 93. The catalyst of any one of embodiments 76 to 92, wherein 0 to 0.01% by weight, preferably 0 to 0.001% by weight, more preferably 0 to 0.0001% by weight, of the coating consists of platinum, preferably platinum and palladium, more preferably platinum, palladium and rhodium, more preferably platinum group metals.
[0214] 94. The catalyst according to any one of embodiments 76 to 93, wherein 95 to 100% by weight, preferably 98 to 100% by weight, more preferably 99 to 100% by weight, and more preferably 99.5 to 100% by weight, of the coating consists of one or more of vanadium oxide and tungsten oxide, and preferably a mixed oxide comprising cerium, supported on an oxide support, and more preferably an oxide binder as defined in any one of embodiments 87 to 89.
[0215] 95. The catalyst of any one of embodiments 76 to 94, wherein the coating extends over x% of the axial length of the substrate on the surface of the inner wall from the inlet end to the outlet end or from the outlet end to the inlet end, where x is in the range of 90 to 100, preferably in the range of 95 to 100, and more preferably in the range of 98 to 100.
[0216] 96. The substrate is a flow-through substrate, preferably one or more of a cordierite flow-through substrate and a silicon carbide flow-through substrate, more preferably a cordierite flow-through substrate; or the substrate is a wall-flow substrate, preferably one or more of a cordierite wall-flow substrate and a silicon carbide wall-flow substrate, more preferably a cordierite wall-flow substrate; 96. The catalyst of any one of embodiments 76 to 95, wherein the substrate is more preferably a flow-through substrate, more preferably a cordierite flow-through substrate.
[0217] 97. The catalyst of any one of embodiments 76 to 96, comprising a substrate and a coating.
[0218] 98. A method of using the selective catalytic reduction catalyst of any one of embodiments 76 to 97 for the selective catalytic reduction of nitrogen oxides.
[0219] 99. A method of using an aqueous suspension according to any one of embodiments 1 to 29 for producing a selective catalytic reduction catalyst.
[0220] 100. A method for selective catalytic reduction of nitrogen oxides, comprising: (1) providing an exhaust gas stream from a diesel engine, the exhaust gas stream including NOx; (2) passing the exhaust gas stream provided in (1) through a selective catalytic reduction according to any one of embodiments 76 to 97. A method comprising:
[0221] 101. A method for improving adhesion of a catalyst coating to a substrate in a catalyst, comprising using an aqueous suspension according to any one of embodiments 1 to 29 to produce a catalyst.
[0222] In the context of the present invention, the term "X is one or more of A, B and C" (X is a given characteristic and each of A, B and C represents a specific embodiment of said characteristic) is to be understood as meaning that X is either A, or B, or C, or A and B, or A and C, or B and C, or A and B and C, as disclosed. In this regard, it is noted that the skilled person can transfer the above abstract terms to concrete examples, such as X being a chemical element and A, B and C being specific elements, e.g., Li, Na, and K, or X being a temperature and A, B and C being specific temperatures, e.g., 10°C, 20°C, and 30°C. In this regard, it is further noted that the skilled person can expand the above terms to less specific realizations of said feature, such as "X is one or more of A and B," i.e. disclosing that X is either A, or B, or A and B, or to more specific realizations of said feature, such as "X is one or more of A, B, C and D," i.e. disclosing that X is either A, or B, or C, or D, or A and B, or A and C, or A and D, or B and C, or B and D, or C and D, or A and B and C, or A and B and D, or B and C and D, or A and B and C and D.
[0223] Furthermore, in the context of the present invention, the term "inner wall surface" is to be understood as the "bare" or "bare" or "blank" surface of the wall, i.e. the surface of the wall in its untreated state consisting of the wall material, except for any unavoidable impurities that may be mixed into the surface.
[0224] Furthermore, in the context of the present invention, the term "consists of" in relation to the weight percent of one or more components indicates the weight percent amount of said component(s) relative to 100 weight percent of the entity in question, for example, the expression "0-0.001 weight percent of the coating consists of platinum" indicates that, of the 100 weight percent of the components constituting said coating, 0-0.001 weight percent consists of platinum.
[0225] The present invention is further illustrated by the following Reference Examples, Comparative Examples, and Examples. EXAMPLES
[0226] Reference Example 1: Determination of particle size distribution, Dv10, Dv50, and Dv90 values Particle size distribution was determined by static light scattering using a Sympatec HELOS instrument, and the optical density of the samples ranged from 5 to 10%.
[0227] Reference Example 2 Measurement of BET specific surface area The BET specific surface area was determined according to DIN 66131 or DIN ISO 9277 using liquid nitrogen.
[0228] Reference Example 3 General coating method To coat the flow-through substrate with one or more coatings, the flow-through substrate was immersed vertically into a given portion of the slurry for a specific length of the substrate. In this way, the washcoat was brought into contact with the walls of the substrate. The sample was left in the slurry for a specific period of time, usually 1-10 seconds. A vacuum was applied to draw the slurry into the substrate. The substrate was then removed from the slurry, inverted, and excess slurry was allowed to drain from the substrate, which was then removed from the substrate by blowing (in the direction of the slurry penetration) with compressed air.
[0229] Reference Example 4 Determination of the average porosity of uncoated substrates Mercury porosimetry was used to determine the average porosity of the porous wall-flow substrates by mercury intrusion according to DIN 66133 and ISO 15901-1.
[0230] Example 1.1 The present invention (having an oxide support with a bimodal particle size distribution) evening Vanadium-Based SCR Catalysts The aqueous vanadium oxalate solution (removal of all solvent results in 11 wt. % vanadium oxide in water, relative to the weight of the solution) was diluted with distilled water so that the final solute weight percentage of the solution was 3 wt. %. The amount of vanadium oxalate used was calculated so that after calcination, the vanadium oxide, calculated as V2O5, was present at a loading of 2.5% of the loading of the final coating in the catalyst. To this diluted vanadium oxalate mixture was added titania powder (90 wt. % TiO2 and 10 wt. % WO3, BET specific surface area: ca. 90 m2). 2 / g, Dv10: about 0.4 micrometers, Dv50: about 1 micrometer, Dv90: about 2.5 micrometers and Dv99: about 15.3 micrometers, and a bimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein, said particle size distribution curve including a first peak having a maximum at about 1.25 micrometers and a second peak having a maximum at about 14 micrometers). In addition, an organic dispersant (acrylic polymer) solution (having a pH of 8) was added to the suspension, in which 39% by weight of the solution's weight was acrylic polymer. The amount of dispersant mixture was calculated so that after calcination, the amount of dispersant mixture was 5% by weight of the total weight of titania + tungsten oxide in the catalyst. The resulting suspension was stirred for a few minutes and the pH was adjusted to about 5.5 by adding an ammonium-hydroxide solution. Distilled water was further added to obtain a suspension with a solid content of up to 45.3% by weight.
[0231] The final loading in the calcined SiO2 catalyst was then 0.21 g / in 3Aqueous colloidal silica (having a solids content of 40% by weight) was added to the resulting suspension along with additional distilled water in an amount such that the final solids content of the suspension was 45% by weight. The particles of the suspension exhibited a bimodal particle size distribution characterized by a particle size distribution curve determined in accordance with Reference Example 1 herein, the particle size distribution curve including a first peak having a maximum value at about 1.25 micrometers and a second peak having a maximum value at about 14 micrometers. The particle size distribution curve of the particles of the suspension is shown in FIG.
[0232] Following the procedure described in Example 3, an uncoated honeycomb flow-through cordierite monolith substrate (average porosity 35%, cylindrical substrate 10.5 inches (26.67 cm) diameter x 6 inches (15.24 cm) length, with a 400 / (2.54) per square centimeter coating thickness) was prepared. 2 The resulting suspension was coated onto a 100% length of the substrate (having 10 cells and a wall thickness of 0.10 millimeters (4 mils)) from the inlet end of the substrate toward the outlet end. The coated substrate was dried in stages between 110°C and 130°C for a total of 30 minutes (to remove up to 80% of the water) and calcined in air for 4 hours, of which approximately 30 minutes was at 450°C. The coated substrate was coated a second time with the suspension from the outlet end of the substrate toward the inlet end over 100% of the substrate's length, then dried in stages between 110°C and 130°C for a total of 30 minutes (to remove up to 80% of the water) and calcined in air for 4 hours, of which approximately 30 minutes was at 450°C. The final loading of the coating in the catalyst after calcination was 4.5 g / in 3 which is 4.18g / in 3 Titania + WO3, 0.11g / in 3 of vanadium (calculated as V2O5) and 0.21 g / in 3 It contained SiO2.
[0233] Comparative Example 1 Vanadium-Based SCR Catalyst Not According to the Invention (Not Having a Bimodal Particle Size Distribution Component) An aqueous vanadium oxalate solution (removal of all solvents results in 11 wt. % vanadium oxide based on the weight of the solution) was diluted in distilled water such that upon calcination the final solution would result in 3.1 wt. % vanadium oxide based on the weight of the aqueous solution. The amount of vanadium oxalate used was calculated such that vanadium oxide, calculated as V2O5, was present at a loading of 4% of the final coating loading in the catalyst after calcination. An acrylic acid based organic dispersant (acrylic polymer) solution having a pH of 8 was added, where 39 wt. % of the weight of the solution was acrylic polymer, to form a mixture. The amount of dispersant mixture was calculated such that the amount of dispersant mixture would be 5 wt. % of the total weight of the coating in the catalyst after calcination.
[0234] Titania powder (87% by mass of TiO2, containing 8% by mass of WO3 and 5% by mass of SiO2, BET specific surface area: approx. 85 m 2 / g, Dv10: 0.7 micrometers, Dv50: 1.3 micrometers, Dv90: 2.5 micrometers and Dv99: about 5 micrometers) was added to the resulting mixture to form a suspension. After calcination, the final loading of titania + tungsten oxide + silica in the catalyst was 4.11 g / in 3 The pH of the suspension was adjusted to about 7.0. Additional distilled water was added to bring the solids content of the suspension up to 40.6 wt. %. A second organic-based dispersant (organic polymer) mixture was added to the suspension, which had a solids content of 31 wt. %. This second dispersant mixture was added in an amount of 1 wt. % of the final coating loading in the catalyst.
[0235] Finally, aqueous colloidal silica (40% solids by weight) was added to the suspension along with additional distilled water to obtain a final suspension with a solids content of 39% by weight. The amount of colloidal silica used was calculated so that the final SiO2 loading (from colloidal silica) was 5% of the final loading of titania + tungsten oxide + silica in the catalyst after calcination. The particles of the suspension exhibited a monomodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein, which included a peak with a maximum value at about 1.7 micrometers. The particle size distribution of the particles of the final suspension is shown in Figure 2. The pH of the suspension was measured and adjusted to about 7.
[0236] Following the procedure described in Example 3, an uncoated honeycomb flow-through cordierite monolith substrate (average porosity 35%, cylindrical substrate 10.5 inches (26.67 cm) diameter x 6 inches (15.24 cm) length, with a 400 / (2.54) per square centimeter coating thickness) was prepared. 2 The final suspension was coated onto a 100% long substrate (having 100 cells and 0.10 millimeter (4 mil) wall thickness) from the inlet end of the substrate toward the outlet end. The coated substrate was dried in stages between 110°C and 130°C for a total of 30 minutes (to remove up to 80% of the water) and calcined in air for 4 hours, of which approximately 30 minutes was at 450°C. The coated substrate was coated a second time with the suspension from the outlet end of the substrate toward the inlet end over 100% of the substrate's length, then dried in stages between 110°C and 130°C for a total of 30 minutes (to remove up to 80% of the water) and calcined in air for 4 hours, of which approximately 30 minutes was at 450°C. The final loading of the coating in the catalyst after calcination was 4.5 g / in 3 which is 4.11g / in 3 Titanium dioxide + tungsten oxide + silica, 0.18g / in 3 of vanadium (calculated as V2O5), 0.21 g / in 3 of SiO2 (derived from colloidal silica).
[0237] Example 1.2 Vanadium-based SCR catalyst (with bimodal particle size distribution mixed oxide) A powder of mixed oxides of Ce and Zr (40% by mass Ce calculated as CeO2, 50% by mass Zr (about 49% by mass) and Hf calculated as ZrO2 and HfO2, respectively), 5% by mass La2O3, and 5% by mass Pr6O 11 BET specific surface area: approx. 80 m 2 / g, Dv10: about 1 micrometer, Dv50: about 4 micrometer, Dv90: about 21 micrometer and Dv99: about 37 micrometer, and a bimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein, the particle size distribution curve including a first peak having a maximum value at about 2.25 micrometer and a second peak having a maximum value at 20 micrometer as shown in Figure 3) was added to distilled water and tartaric acid (1 g tartaric acid per 4000 g mixed oxides). The resulting suspension was milled using a continuous milling device so that the particles of the suspension had a Dv10 of 0.98 micrometers, the particles of the suspension had a Dv50 of 3.06 micrometers, the particles of the suspension had a Dv90 of 13.61 micrometers and the particles of the suspension had a Dv99 of 27.34 micrometers. The resulting suspension exhibited a bimodal particle size distribution characterized by a particle size distribution curve determined according to Example 1 herein, which included a first peak having a maximum at about 2.25 micrometers and a second peak having a maximum at about 15 micrometers, as shown in Figure 4. The amount of mixed oxides of Ce and Zr was such that the loading in the catalyst was 1 g / in 3 The solid content of the obtained suspension was 35% by mass.
[0238] Separately, the aqueous vanadium oxalate solution (removal of all solvents results in 11% vanadium oxide by weight relative to the weight of the aqueous solution) was diluted with distilled water such that upon calcination the final solution would result in 3.3% vanadium oxide by weight relative to the weight of the aqueous solution. The amount of vanadium oxalate used was calculated such that the vanadium oxide, calculated as V2O5, was present at a loading of 4.5% of the loading of titania + tungsten oxide + silica in the catalyst after calcination. An acrylic acid-based organic dispersant (acrylic polymer) solution having a pH of 8 was added to the vanadium-containing solution, where 39% by weight of the solution's weight was acrylic polymer. The amount of dispersant mixture was calculated such that the amount of dispersant mixture was 5% by weight of the total weight of the coating in the catalyst after calcination. Titania powder (87% by weight TiO2 contains 8% by weight WO3 and 5% by weight SiO2, BET specific surface area: about 85 m 2 / g, Dv10: about 0.7 micrometers, Dv50: about 1.3 micrometers, Dv90: about 2.5 micrometers and Dv99: about 4.8 micrometers) was added to the resulting mixture to form a suspension. After calcination, the final loading of titania + tungsten oxide + silica in the catalyst was 3.2 g / in 3 The resulting suspension had a solids content of about 42.3% by weight.
[0239] The suspension containing Ce-Zr and the suspension containing vanadium and titania were mixed and stirred with a stirring impeller. The pH of the resulting suspension was measured and adjusted to about 6.5. Additional distilled water was added to bring the solid content of the suspension to 40% by weight. The viscosity of the suspension was 50-100 mPa at 300 revolutions per second. *s. Finally, aqueous colloidal silica (40% solids by weight) was added to the suspension along with additional distilled water to obtain a final suspension with 40% solids by weight. The amount of colloidal silica used was calculated so that the final SiO2 loading (from colloidal silica) was 5% of the final loading of titania + tungsten oxide + silica in the catalyst after calcination. The particle size distribution of the particles of the suspension is shown in Figure 5. The particles of the suspension exhibit a bimodal particle size distribution characterized by a particle size distribution curve determined according to Reference Example 1 herein, the particle size distribution curve including a first peak having a maximum value at about 1.75 micrometers and a second peak having a maximum value at about 8 micrometers. The pH of the suspension was measured and adjusted to about 7.
[0240] Following the procedure described in Example 3, an uncoated honeycomb flow-through cordierite monolith substrate (average porosity 35%, cylindrical substrate 10.5 inches (26.67 cm) diameter x 6 inches (15.24 cm) length, with a 400 / (2.54) per square centimeter coating thickness) was prepared. 2 The final suspension was coated onto a 100% length substrate (having 10 cells and 0.10 millimeter (4 mil) wall thickness) from the inlet end of the substrate toward the outlet end. The coated substrate was dried in stages between 110°C and 130°C for a total of 30 minutes (to remove up to 80% of the water) and calcined in air for 4 hours, of which approximately 30 minutes was at 450°C. The coated substrate was coated a second time with the suspension from the outlet end of the substrate toward the inlet end over 100% of the substrate's length, then dried in stages between 110°C and 130°C for a total of 30 minutes (to remove up to 80% of the water) and calcined in air for 4 hours, of which approximately 30 minutes was at 450°C. The final loading of coating in the catalyst after calcination was 4.5 g / in 3 which is 3.2g / in 3 Titania + WO3 + SiO2, 0.14g / in 3 of vanadium (calculated as V2O5), 1 g / in 3 Ce / Zr mixed oxide, 0.16g / in 3of SiO2 (derived from colloidal silica).
[0241] Example 2 Washcoat Adhesion Test Cores were drilled from each of the catalysts (coated substrates) obtained in Comparative Example 1, Examples 1.1 and 1.2. Each of the cores had a length of 3 inches and a diameter of 1 inch. The three cores obtained were weighed. The cores of each sample of Comparative Example 1, Examples 1.1 and 1.2 were exposed to a high pressure air treatment (2 bar) so that air was forced evenly through the cores. After the air flow was stopped, the cores were weighed again. The masses before and after the same high pressure air treatment were compared. The results for each of the three cores are shown in Figure 6.
[0242] As can be seen from FIG. 6, the catalyst coating of Example 1.1 according to the invention and the catalyst coating of Example 1.2 show a washcoat loss of less than 1.5%, which indicates good washcoat adhesion, while the catalyst coating of Comparative Example 1 shows a higher washcoat loss of about 18%. Without wishing to be bound by any theory, it is believed that this is due to the presence of a bimodal particle size distribution in the suspensions of Examples 1.1 and 1.2 of the invention used for coating. The difference between the catalyst coating of Example 1.2 and the catalyst coating of Comparative Example 1 is the presence of a Ce / Zr mixed oxide with a bimodal particle size distribution. Thus, the presence of this particular mixed oxide in the coating suspension makes it possible to greatly improve the washcoat adhesion on the substrate. Furthermore, the difference between the catalyst coating of Example 1.2 and the catalyst coating of Example 1.1 is the type of titania support and the presence of a bimodal Ce-containing mixed oxide. In particular, in the coating of Example 1.1, the titania support is a titania support with a bimodal particle size distribution, whereas the support used in Example 1.2 has a monomodal particle size distribution. Thus, it is demonstrated that only the presence of a bimodal particle size distribution Ce-containing mixed oxide (binder) can make it possible to obtain a similar washcoat adhesion compared to a coating containing a much higher proportion of a bimodal particle size distribution oxide support. Thus, Example 2 demonstrates that the use of a bimodal particle size distribution in the suspension before coating allows a significant increase in washcoat adhesion.
[0243] Example 3.1 The present invention evening Vanadium-based SCR catalyst (with bimodal particle size distribution oxide support) The catalyst of Example 3.1 was an uncoated honeycomb flow-through cordierite monolith substrate (a cylindrical substrate with a diameter of 33.02 cm (13 inches) and a length of 15.24 cm (6 inches) and a 400 / (2.54) per square centimeter) 2 The catalyst was prepared as in Example 1.1, except that the catalyst had 10 cells and a wall thickness of 0.10 millimeters (4 mils).
[0244] Example 3.2 Vanadium-based SCR catalyst (with bimodal particle size distribution Ce-containing mixed oxide) The catalyst of Example 3.2 was an uncoated honeycomb flow-through cordierite monolith substrate (a cylindrical substrate with a diameter of 33.02 cm (13 inches) and a length of 15.24 cm (6 inches) and a 400 / (2.54) per square centimeter) 2 The catalyst was prepared as in Example 1.2, except that the catalyst had 10 cells and a wall thickness of 0.10 millimeters (4 mils).
[0245] Example 4 Performance Evaluation-DeNOx The SCR catalysts of Examples 3.1 and 3.2 were tested on a 13 L motor. For the tests, three diesel oxidation catalysts (DOCs) (each DOC was 12 inches by 6 inches and had a mass of 20 g / ft 3 A urea injector (with Pt) was fixed upstream of the two SCR catalysts of example 3.2, achieving 80% NO2 / NOx at the SCR inlet. The two SCR catalysts were fixed downstream of the DOC and in series with the urea injector. An SCR-inlet temperature of 270°C was achieved. Once the system reached a steady state, urea was fed in increasing stoichiometric ratios until a steady state was achieved again. The same was done with the SCR catalyst prepared according to example 3.2. The results are shown in Figure 7.
[0246] As can be seen from Figure 7, the results show that the baseline performance plateau is reached even before 100% stoichiometry (although it does respond more quickly than the Ce / Zr variant). The advantage of using the mixed Ce / Zr is that a large oversupply of urea ultimately results in higher conversion than baseline at very high NO2 concentrations.
[0247] Cited literature -US2015 / 0005158 A1
Claims
1. An aqueous suspension comprising water, one or more sources of vanadium oxide and tungsten oxide, and particles of an oxide support, 1. The aqueous suspension, wherein the particles of the aqueous suspension exhibit a multimodal particle size distribution characterized by a particle size distribution curve including a first peak having a peak particle size value M(I) in the range of 1.25 to 2 micrometers and a second peak having a peak particle size value M(II) in the range of 6.25 to 15 micrometers, where (M(I) / μm) / (M(II) / μm)<1.
2. 2. The suspension of claim 1, wherein the particles of the aqueous suspension exhibit a bimodal particle size distribution.
3. further comprising particles of a mixed oxide containing cerium; 3. The suspension of claim 1 or 2, wherein the mixed oxide further comprises one or more of zirconium, niobium, molybdenum, lanthanum, yttrium, neodymium, praseodymium and hafnium.
4. 4. The suspension of claim 3, wherein the mixed oxide particles exhibit a unimodal or multimodal particle size distribution.
5. 5. The suspension according to claim 1, wherein (M(II) / μm)-(M(I) / μm)≧0.
5.
6. 6. A suspension according to any one of claims 1 to 5, wherein the particles of the aqueous suspension have a Dv50 in the range of 0.2 to 10 micrometers.
7. The aqueous suspension contains, in an amount ranging from 1.5 to 8% by weight, based on the weight of the oxide support, 2 O 5 7. The suspension of claim 1 , comprising a source of vanadium oxide, calculated as:
8. the particles of said oxide support exhibit a monomodal particle size distribution; or 8. The suspension according to claim 1 , wherein the particles of the oxide support exhibit a multimodal particle size distribution.
9. 9. The suspension of any one of claims 1 to 8, wherein the oxide support comprises one or more of titanium, silicon, zirconium, and tungsten.
10. 10. The suspension of any one of claims 1 to 9, wherein the aqueous suspension further comprises a source of oxidized binder.
11. A process for producing an aqueous suspension according to any one of claims 1 to 10, comprising the steps of: (i) preparing an aqueous suspension comprising water and particles of a mixed oxide comprising cerium, said mixed oxide being as defined in claim 3, and wherein the particles of said mixed oxide contained in said aqueous suspension exhibit a monomodal particle size distribution; or A process for producing an aqueous suspension comprising water and particles of a mixed oxide comprising cerium, said mixed oxide being the mixed oxide of claim 3, said particles of said mixed oxide contained in said aqueous suspension exhibiting a multimodal particle size distribution, characterized by a particle size distribution curve comprising a first peak having a peak particle size value M1 in the range of 0.5 to 20 micrometers and a second peak having a peak particle size M2 in the range of 1 to 50 micrometers, where (M1 / μm) / (M2 / μm)<1; (ii) producing an aqueous suspension comprising water and one or more sources of vanadium oxide and tungsten oxide, and further comprising particles of an oxide support, wherein the particles of the oxide support contained in the aqueous suspension exhibit a unimodal particle size distribution characterized by a particle size distribution curve including a peak having a maximum value in the range of 0.5 to 5 micrometers, or the particles of the oxide support contained in the aqueous suspension exhibit a multimodal particle size distribution; (iii) mixing the suspension from (ii) with the suspension from (i) to obtain an aqueous suspension comprising water, one or more sources of vanadium oxide and tungsten oxide, particles of an oxide support, and particles of a mixed oxide comprising cerium, wherein the particles of said aqueous suspension exhibit a multimodal particle size distribution comprising a first peak having a peak particle size value M(I) in the range of 1.25 to 2.5 micrometers and a second peak having a peak particle size M(II) in the range of 6.25 to 15 micrometers, characterized by a particle size distribution curve where (M(I) / μm) / (M(II) / μm)<1. The method includes:
12. (i) preparing the aqueous suspension according to (i.1) providing particles of said mixed oxide comprising cerium, said mixed oxide particles exhibiting a multimodal particle size distribution comprising a first peak having a peak particle size value M1' in the range of 0.5 to 30 micrometers and a second peak having a peak particle size value M2' in the range of 1 to 60 micrometers, characterized by a particle size distribution curve where (M1' / μm) / (M2' / μm)<1; (i.2) preparing an aqueous suspension comprising suspending the particles provided in (i.1) in water, (i.3) milling the aqueous suspension produced in (i.2) until the particles of the aqueous suspension exhibit a multimodal particle size distribution characterized by a particle size distribution curve comprising a first peak having a peak particle size M1 and a second peak having a peak particle size M2, where (M1 / μm) / (M2 / μm)<1, and (M2 / μm)<(M2' / μm) and / or (M1 / μm)<(M1' / μm). The method of claim 11 , comprising:
13. 13. The method of claim 12, wherein the mixed oxide particles provided in (i.1) have a Dv50 in the range of 1 to 30 micrometers.
14. 1. A method for producing a selective catalytic reduction catalyst, comprising: (a) producing an aqueous suspension according to any one of claims 1 to 10 according to a method according to any one of claims 11 to 13, (b) disposing the suspension obtained in (a) on a surface of an interior wall of the substrate including an inlet end, an outlet end, an axial length of the substrate extending between the inlet end and the outlet end, and a plurality of passages defined by the interior wall of the substrate extending therethrough, wherein an interface between the passages and the interior wall is defined by a surface of the interior wall; and drying the substrate with the suspension disposed thereon; (c) calcining the substrate obtained in (b). The method includes:
Citation Information
Patent Citations
Dispersing liquid for coating exhaust gas catalyst
JP1994007683A
Emission gas treatment system with nsr and scr catalysts
JP2007527314A
Manufacturing method of denitration catalyst
JP2008155133A
Non-zeolite base metal SCR catalyst
JP2010531227A
Preparation method for denitration catalyst
JP2012200667A